RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Simulation of quasi-static fracture in fractured rock materials using a two-stage joint algorithm within peridynamics - Xiaohua Huang; Shuang Li; Ting Hu; Yanli Jin; Zhi Zheng; Lie Yan (Computers and Geotechnics, 2027)

Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

Effect of iron homeostasis on modulating cold-associated ferroptosis related response and sterile inflammation in silver pomfret (Pampus argenteus) - Yunkang Wu; Yuanbo Li; Ting Chen; Wuqiang Xia; Denggui Chen; Xiang Chen; Yajun Wang; Xiaojun Yan; Jiabao Hu (Aquaculture, 2027)

Genome-wide identification of the OfMYC gene family and putative involvement of OfMYC10/16 in petal senescence via an EIL–ERF–ROS regulatory module - Hui Xia; Qinyu Yan; Ting Zhang; Jie Yang; Hongguo Chen; Xuan Cai; Jingjing Zou; Zeqing Li; Xiangling Zeng; Yingting Zhang (Postharvest Biology and Technology, 2026)

Development of a sandwich ELISA analysis platform using dual nanobodies for quantitative detection of bovine lactoferrin in dairy products - Li Cao; Ting Zhang; Yan-Ping Li; Qinghua He; Zhui Tu (International Dairy Journal, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Contrasting redox-related physiological responses associated with HaGATA23 and HaGATA36 during Orobanche cumana parasitism in sunflower (Helianthus annuus L.) - Yan Fu; Ting Zhou; Shuo Zhang; Shuowei Su; Lei Shen; Ying Li; Wenya Zhang; Ahsan Ayyaz; Hongju Sun; Ling Xu (Plant Science, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Integrated analysis of muscle proteomics and neurotransmitter-targeted metabolomics in Penaeus vannamei infected with Enterocytozoon hepatopenaei (EHP) - Zhipeng Yin; Yajie Tian; Chuanyu He; Fan Yang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Aquaculture, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Garlic aqueous extract promotes the enrichment and horizontal transfer of high-risk antibiotic resistance genes during composting - Jun Xie; Guangfu Yan; Xiaodong Zhao; Xun Qian; Guanyu Zheng; Ting Hu; Lan Jiang; Pingmei Yan; Pengyu Zhao; Geng Liu; Xiaojing Li (Journal of Environmental Chemical Engineering, 2026)

Natural deep eutectic solvent-extracted propolis bioactives and ZIF-L integrated PVA films for active packaging and oyster preservation - Tian Du; Qing-Ping Zheng; Ye-Ting Wang; Meng Li; Yan-Zhen Zheng (Food Research International, 2026)

Dynamic characterization of volatile profiles and intelligent discrimination of raw Milk under frozen storage using non-targeted volatile metabolomics and machine learning - Ken Lu; Liqiong Niu; Ting Wen; Zhicong An; Chen Liu; Jiangfei Chai; Hongliang Li; Bei Zhou; Yongjing Bie; Chaokun Wei; Yan Ping Chen; Yuan Liu (Food Research International, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Rice bran-based bio-adsorbents: optimizing modification protocols and adsorption kinetics for cadmium decontamination - Juan Li; Yangmei Xue; Yan Shao; Shuai Yang; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Long-term faba bean–wheat intercropping mitigates continuous monocropping-induced decline in faba bean seed quality by improving rhizosphere nutrient availability - Ting Li; Bijie Hu; You Huang; Taiqin Liu; Jinlin Pu; Yan Dong (Field Crops Research, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

A bioinspired flavin-based catalytic construct enabling intracellular NAD+/NADH redox regulation for mitigating skin aging - Jiani Xiang; Qian Ling; Li Yan; Ying Xia; Peizhen Lou; Zhen-Gang Wang; Ting Li; Huiling Wu (Chemical Engineering Journal, 2026)

Interfacial electronic coupling in Bi2O3/COF heterostructures for high-performance supercapacitors - Rui Zhang; Hong-xia Gao; Yu-ting Zhao; Li Li; Yan Lv; Xue-yan Wu; Jixi Guo; Rui Xue (Chemical Engineering Journal, 2026)

Trade-off between structural resilience and kinetics induced by N2-plasma activated CN− vacancies in high-entropy Prussian blue cathodes for sodium-ion storage - Qiang Liu; Yan-Jiang Liu; Miao-Yu Li; Ting-Liang Xie; Hao-Tian Tong; Bo Jin; Shuang-Feng Yin (Chemical Engineering Journal, 2026)

Quantitative shear-window engineering enables scalable biomanufacturing of functional mesenchymal stem cell-derived exosomes - Wei-feng Li; Kai-jie Xia; Yan Xin; Jay Liu; Yu-ting Sun; Kamran Ashraf; Yu-wen Hu; Touseef Ur Rehman; Fan Gao; Shao-yong Zhuang; Mei-jin Guo; Ali Mohsin (Chemical Engineering Journal, 2026)

Hydrogen-bond–mediated directional adsorption and acid–base synergy promote the transfer hydrogenation of levulinic acid to γ-valerolactone - Jianhua Wang; Jie Li; Ting Gan; Qiong Xu; Wenzhou Zhong; Dulin Yin; Xianxiang Liu; Hao Yan (Bioresource Technology, 2026)

Tetrahydroisoquinoline alkaloids from the fruits of Piper nigrum and their chemotaxonomic significance - Yan Li; Bin Chen; Wei-Cheng Hu; Fu Li; Ting Shen (Biochemical Systematics and Ecology, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Intrinsically flame-retardant, transparent, mechanically robust and flexible waterborne polyurethanes regulated by phosphorus chemical environments - Yu Li; Hao-Ran Jiang; Hao-Jie Shi; Yu-Ting Yang; Hao-Xin Niu; Meng-Qi Jia; Ying Yan; Yuan Hu; Zhou Gui; Xin Wang (Chemical Engineering Journal, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Postbiotics mitigate translucent post-larvae disease (TPD) in Penaeus vannamei by reinforcing hepatopancreatic cytoskeletal integrity against VHVP-2 toxin - Wenqiang Li; Shuang Liu; Jin Yan; Ping Li; Tingting Xu; Jin-Seng Lin; Hsiao-Tung Chang; Ting-Yu Lee; Qingli Zhang (Aquaculture, 2026)

Thermally synergized electron shuttling via Cu-O-Fe bridge redirects H2O2 activation pathways - Wei-bang Xie; Dan Zheng; Kai-kai Chen; Jing Liu; Wen-jie Ju; Zhong-ting Hu; Mian Hu; Chun-shan Lu; Zhi-yan Pan; Xiao-nian Li (Water Research, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Multi-proxy evidence for the initiation of Yellow River integration through Sanmen Gorge at ∼1.8 Ma: Insights from borehole YJ-1 in the Yuncheng Basin, Fenwei Graben - Ting Huang; Zhenhong Li; Xiaopeng Dong; Shiyu Zhang; Yan Guan; Yong Lei; Zhonghai Wu; Zongxiu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Transcriptome analysis provides molecular evidence for muscle growth regulation in Litopenaeus vannamei infected with Ecytonucleospora hepatopenaei (EHP) - Chuanyu He; Zhipeng Yin; Yajie Tian; Fan Yang; Zheng Cao; Cuixia Wang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Journal of Invertebrate Pathology, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

Glucose glycosylation enhances the functional properties of grass carp scale gelatin-derived TIPs via gut microbiota and metabolite regulation - Zi-Zi Hu; Ting-Ting Wu; Xin Li; Chun-Yan Peng; Su-Su Ye; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2026)

CmPah1 coordinates lipid metabolism and fruiting body formation in the edible and medicinal fungus Cordyceps militaris - Bing Li; Tianhao Shen; Dapeng Bao; Yan Li; Wenjie Chen; Hongyu Chen; Youran Shao; Ting Guo; Jianing Wan; Gen Zou; Ying Wang (Food Bioscience, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Plasma-engineered chitosan couples red-light bioenergetics to diabetic wound regeneration through programmable microenvironments - Lekshmi Rethi; Hoa Duc Chau; Erlina Febriani; Yan-Ting Chen; Szu-Yu Tung; Pei-Ru Jheng; Yu-Wen Tseng; Rou Li; Min-Lang Tsai; Chun-Chi Chang; Van Khiet Pham; Hieu Trung Nguyen; et al. (Carbohydrate Polymers, 2026)

Correction: The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

The narrow-spectrum circadian rhythm promotes the photosynthesis and pigment accumulation of celery within two days (light/dark: 12 h/12 h) - Chen Chen; Li-Xiang Wang; Meng-Yao Li; Guo-Fei Tan; Ting Huang; Jing Zhuang; Jin-Song Xiong; Jun Yan; Ai-Sheng Xiong (Journal of Photochemistry and Photobiology B: Biology, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Associations between prenatal exposure to indoor air pollution and ambient particulate matter with infant growth - Jinlang Lyu; Tiantian Li; Shuang Zhou; Xin Yuan; Zheng Bao; Na Han; Gongbo Chen; Yuelong Ji; Qin Li; Jue Liu; Hui Wang; Jianlin Hu; et al. (Journal of Environmental Sciences, 2026)

Lead isotopic provenance and migration in multiple environmental media of the Muztagh Glacial Watershed, Pamir Plateau - Zhiwen Dong; Xiaoli Liu; Fangzhou Li; Lunche Wang; Ting Wei; Yan Yan (Global and Planetary Change, 2026)

Multi-strain fermentation alters nutrient composition and phase distribution of metabolites in black highland barley - Yan Shao; Bin Dang; Xijuan Yang; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Chemistry, 2026)

Gas-liquid two-phase flow pattern identification based on HHT and SVM-assisted optical carrier microwave interferometry - Songlin Li; Ting Xue; Yan Wu (Chemical Engineering Journal, 2026)

MECP2T203M mutation disrupts neurogenesis in human cerebral organoids by altering chromatin dynamics and transcriptional regulation - Zhihong Song; Qian Zhu; Rui Yang; Huihui Jiang; Ying Li; Liping Chen; Ting Wang; Yan Wu; Yan Liu; Haitao Wu (Science China Life Sciences, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Systematic characterization of FBP gene family in Saccharum reveals ScFBP3 as a key regulator of sucrose-mediated plant branching - Huiwen Zhou; Hanmin Luo; Minyi Wei; Ting Luo; Faqian Xiong; Ming Li; Lihang Qiu; Haifeng Yan (Plant Science, 2026)

PM2.5-bound organophosphate esters and childhood attention-deficit hyperactivity disorder symptoms: A population-based study from China - Chu Chu; Xuan Liu; Yan-Xu Chen; Jia-Xiang Dong; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Xia Liang; Yang Zhou; Muhammad Amjad; Yan Yang (NeuroToxicology, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

First-trimester profiling of maternal plasma metals and vitamins in relation to gestational hypertension - Ting Wu; Tao Li; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Environmental Research, 2026)

Nitrogen-Phosphorus Co-Doped Biochar for Persulfate Activation in Sulfadiazine Degradation: Degradation Performance, Mechanism and Toxicity Assessment - Weiwei Yu; Rongqi Liu; Ting Ai; Yufeng Mao; Jiajie Li; Lu Lv; Dan Liu; Yan Luo; Wang Xin; Man Luo; Boyu Liu (Water, Air, & Soil Pollution, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

Amino acid and appendicular skeletal muscle mass insufficiency are associated to cognitive decline in Chinese population - Ting Tang; Shuxian Zhang; Yanni Pu; Siquan Li; Bin Jiang; Huiting Liang; Kunmu Zheng; Yan Zheng; He Huang; Jin Li; Xiaodong Pan (GeroScience, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Mangrove species act as potential biofilters for legacy organochlorine pesticides: evidence from tissue-specific accumulation in the Zhangjiang Estuary - Nemin Luo; Ting Fang; Yingying Qian; Lei Wang; Wenhui Lin; Rongrong Song; Guoxin Li; Fengrun Wu; Xiaoqing Chen; Mingyuan Lin; Yan Lin (Marine Environmental Research, 2026)

Global evidence on vitamins in human milk: A 2002–2022 systematic review with a focus on China and implications for maternal diet and infant formula - Yan Yang; Xinggang Ni; Nian Liu; Quanzhang Li; Qi Fang; Ignatius Man-Yau Szeto; Sufang Duan; Teng Wei; Tianyu Rao; Zeyuan Deng; Ting Li; Jing Li (Food Research International, 2026)

Comprehensive insights into AphA-induced physiological alterations and molecular pathways in Vibrio alginolyticus - Yanni Zhao; Zi Wang; Xuan Wu; Hua Li; Ningning Zhou; Meiru Yan; Ting Shao; Xuefeng Chen; Huan Liu (Food Bioscience, 2026)

Heteroprotein complex coacervation of ovotransferrin and lysozyme: Structural properties, interface behavior and foam properties - Ting Zhang; Yinuo Jin; Yulu Li; Jiaxiao Zhai; Jie Wei; Yutong Zhang; Zhaohui Yan; Jingbo Liu; Xuanting Liu (Food Hydrocolloids, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Genome-wide analysis of sunflower (Helianthus annuus) and Orobanche cumana reveals HaEXLA2 and HaEXLB2 as negative regulators of lignin-based resistance - Lei Shen; Yi Duan; Ying Li; Wenya Zhang; Yan Fu; Ting Zhou; Hongju Sun; Ahsan Ayyaz; Ling Xu (Plant Cell Reports, 2026)

Effects of continuous light and skeleton photoperiods on photosynthesis and circadian rhythm in celery - Chen Chen; Ting Huang; Li-Xiang Wang; Meng-Yao Li; Guo-Fei Tan; Jing Zhuang; Jin-Song Xiong; Jun Yan; Ai-Sheng Xiong (Biotechnology Letters, 2026)

Fungal co-cultivation reshapes salt stress adaptation in the cyanobacterium Synechococcus elongatus PCC 7942 - Ting Wang; Yuexuan Wang; Shujuan Wang; Yan Che; Tuanjie Che; Jie Feng; Tingting Li (Algal Research, 2026)

KDM3A Modulates Trastuzumab Resistance in HER2− Positive Breast Cancer Cells via the PI3K/AKT/ERK Pathway - Yuanxing Han; Jiayi Guo; Ting Yang; Xuewen Liu; Honghuo Yan; Yuanzhang Li; Juan Yao (Biochemical Genetics, 2026)

Fast-response Phosphorescence Sensor for Dissolved Oxygen Detection Based on PtOEP/TiO2/CB@PFFE Sensing Film - Jia Xiao; Minmin Han; Ting Li; Baohua Yue; Liuming Yan (Journal of Fluorescence, 2026)

Red Sea bream iridovirus (RSIV) infection elicits cell death modes—Apoptosis and ferroptosis in silver Pomfret (Pampus argenteus) - Yuanbo Li; Youyi Zhang; Wuqiang Xia; Ting Chen; Zukang Feng; Denggui Chen; Fangjun Xu; Man Zhang; Yajun Wang; Xiaojun Yan; Jiabao Hu (Aquaculture, 2026)

A comprehensive functional landscape of PRV replication and pathogenesis revealed by genome-wide transposon mutagenesis - Wanwan Yan; Keyue Ruan; Lingchao Chen; Songnan Li; Ting Liu; Wu Tong; Fei Gao; Lingxue Yu; Ning Kong; Guangzhi Tong; Hao Zheng (Veterinary Microbiology, 2026)

Giardia duodenalis cysts induce bovine neutrophil extracellular trap formation - Yifei Li; Hongsen Yu; Tianyu Li; Xuhai Li; Ting Wu; Xiangyu Yan; Qixi Li; Chenhan Bu; Qi Sun; Jingjing Wang; Ershun Zhou; Zhengtao Yang (Veterinary Parasitology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Sustainable catalyst design: Magnesia slag-doped MS-LDHs fabricated via pulsed laser trapping for efficient and green Cr(VI) adsorption - Ren-yun Zhang; Yan Liu; Zhi-yu Fan; Hong-xuan Xing; Ji-dong Li; Qiu-yu Huang; Zhe Jin; Ting-an Zhang (Journal of Cleaner Production, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Association between maternal physical activity and casein content in breast milk from the YI cohort: A preterm and term infant comparison - Jianlan Xue; Ting Li; Yan Feng; Xinyue Wang; Sufang Duan; Xiaoqin Luo; Jianhua Ma; Li Su (International Dairy Journal, 2026)

Targeted design and controllable assembly of egg white protein complexes guided by phase behavior: Thermal stability and processing properties of ovotransferrin-lysozyme heteroprotein complexes - Yinuo Jin; Ting Zhang; Meng Sun; Yulu Li; Yutong Zhang; Zhaohui Yan; Jingbo Liu; Dongyan Chen; Xuanting Liu (Food Research International, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Quantitative reconstruction of the paleoclimate over the past 200 years in the northern margin of the east Asian summer monsoon, China - Yan-Xia Xue; Hong-Wei Meng; Yu-Zhen Ma; Chao Guo; Ting-Yong Li; Cai-Ming Shen (CATENA, 2026)

Intercropping and exogenous calcium oxide nanoparticles mitigate cadmium toxicity in faba bean - Shunhui Ren; Zhenyu Zhang; Bijie Hu; Yanqin Zhang; Ting Li; Xiaosi Yang; Yan Dong (Plant and Soil, 2026)

An AcMYB10-AcF3GT1/GST1 module restricts anthocyanin synthesis in the fruit flesh of kiwifruit - Xiao-tian Li; Zhi-xia Huang; Yu-xiao Zhai; Ya-ting Guo; Yi-tong Liu; Yan Zhang; Zhu Xie; Andrew C. Allan; Xue-ren Yin; Wen-qiu Wang (Plant Cell Reports, 2026)

Probiotic novel strain Lactobacillus reuteri MRD01 alleviates dextran sulfate sodium-induced colitis in male mice by promoting intestinal barrier integrity - Ying Li; Guoao Ding; Guoan Bao; Xiaojun Lai; Ruxin Ye; Ting Wang; Yujie Du; Ke Xiao; Peng Zhou; Jingjing Wang; Xin Xia; Yan Zhang (Antonie van Leeuwenhoek, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Habitat-shaped microbial life-history strategies and host niche specialization govern soil ARG transfer potential - Houyu Li; Qifan Yang; Ting Liu; Wei Liu; Yinuo Ding; Yan Xu; Zhong Wei (Journal of Hazardous Materials, 2026)

Crystal phase-dependent ZrO2 for fluoride adsorption in hydrochloric acid - Qian Wu; Xin Huang; Shiyu Sun; Yan Li; Fengzhen Liu; Xin Chen; Na Wang; Ting Wang; Zijian Zhou; Bin Lu; Hongxun Hao (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

The occupations of microblade technology populations at Jiangjunbu02 site on the northeastern Tibetan Plateau and their relationships with paleoenvironment changes - Yuanxin Li; Juanting Yao; Xuke Shen; Linxueyi Wang; Yan Zhou; Huan Xia; Dongpeng Lin; Lin Chen; Yongxiu Lu; Jian Wang; Ting Cheng; Yan Zhao; et al. (Science China Earth Sciences, 2026)

Particulate matter generated from electrolysis processes: a review of pollution, formation, and control technologies - Zizhen Ma; Lingyu Li; Qingyuan Hao; Linhua Jiang; Ning Duan; Fuyuan Xu; Lei Duan; Jingkun Jiang; Yanhui Wang; Yan Tan; Huawei Zhang; Ting Liu; et al. (ENGINEERING Environment, 2026)

Source Control of the Seismic Energy Radiation in Rock Blasting - Yongzhen Li; Wenbo Lu; Yang Wang; Ming Chen; Peng Yan; Ting Meng; Jiawei Zheng (Rock Mechanics and Rock Engineering, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Mechanistic insights into soil compaction tolerance in sugarcane: Jasmonate signaling and root structural adaptation underpin compaction resilience - Xiaoyan Liu; Ting Luo; Rui Yan; Yijie Li; Qiang Liang; Ling Yao; Weizan Wang; Prakash Lakshmanan (Soil and Tillage Research, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Association between heavy-duty vehicle pollution exposure and cardiovascular disease: A cohort study of middle-aged and elderly adults - Xin Ma; Juan Hao; Jinghua Wang; Yan Li; Xianjia Ning; Hongjun Mao; Ting Wang (Journal of Environmental Sciences, 2026)

Whole-genome and microbial diversity analyses reveal mechanism of GY8 for enhancing cadmium removal rate of duckweed - Mi Zhang; Yu-Ting Liu; Xiang-Qin Li; Zhi-Qun Chen; Yan Lan; Ai-Juan Tan; Gui-Li Yang (International Biodeterioration & Biodegradation, 2026)

Effects of polystyrene nanoplastics on tomato plant growth, fruit yield and quality - Mingyuan You; Ting Zhou; Jiahui Yan; Jingyue Ma; Tingting Kong; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Food Chemistry, 2026)

Interfacial properties and emulsification performance of methyl-esterified okra polysaccharides - Ting Xu; Bingjie Zhang; Guojun Liu; Hongxu Gao; Panshu Ma; Yepeng Pang; Yuchao Gu; Mingyan Yan; Yinping Li (Food Hydrocolloids, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Genetically Modified Primate Models for Brain Disorder Research - Yi Yang; Jianbang Lin; Mengqi Li; Lixin Yang; Zhonghua Lu; Ting Yan (Neuroscience Bulletin, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Early albumin infusion and mortality in ICU patients with HFpEF: a target trial emulation study - Zhen Wang; Meng-li Li; Nin-jun Zhu; Ting-ting Fan; Yan-mei Zhang (European Journal of Clinical Pharmacology, 2026)

Climate change and transformations of ancient civilization in the Chengdu Plain, Southwest China, during the mid-to-late Holocene - Zhong-Lin Deng; Xin-Yan Li; Ting-Yong Li (Quaternary Science Reviews, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Mitophagy dynamics during oxidative to reductive stress shift potentiates arsenite-induced malignant transformation potential in human keratinocytes - Qianlei Yang; Xingrun Li; Qi Kong; Yuqi Yang; Haixuan Xia; Rui Yan; Xiaoyun Zhang; Hui Lu; Ting Zhang; Chen Zhao; Bohan Xu; Koichi Kato; et al. (Journal of Hazardous Materials, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Deciphering the microbial complexity of Chinese traditional sourdough through integrated learning - Yan Liu; Jinyu Wang; Shiwei Zhou; Feijiang Li; Honghong Cheng; Zheqing Zhu; Jiale Wang; Aowen Liu; Ting Lu; Yujuan Yu; Senmiao Tian; Min Zhang; et al. (Food Research International, 2026)

Mechanisms of absorption and transport of lycopene based on nano-carriers and stereoselectivity - Peng Gao; Ting Liu; Xiaoqin Yan; Chuantian Li; Zhenlin Mao; Jinfang Zhu (Food Bioscience, 2026)

Antimildew and preservation effect of Bacillus velezensis BR-1 during rice storage and its metabolic mechanism - Jiang Li; Ting Wang; Xinyu Zhang; Zeping Lai; Yan Zhao; Junli Zhu (Food Control, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Te-Cu dual adsorption-conversion function cathode enables high-energy-density and long-lifespan liquid metal batteries - Weixin Zhang; Xin He; Ting Zhang; Haomiao Li; Shuai Yan; Xianbo Zhou; Yewei Guo; Min Zhou; Wei Wang; Kai Jiang; Kangli Wang (Chemical Engineering Journal, 2026)

Upcycling industrial waste bischofite to anti-aging agents for asphalt: Macro-properties, micro-characteristics, and statistics-based mechanistic analysis - Hongjun Dong; Zihang Li; Canlin Zhang; Chiara Riccardi; Ting Wang; Peng Jin; Yan Yuan (Chemical Engineering Journal, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Microbial necromass analogues reshape composting humification pathways - Wenjie Chen; Yan Yang; Su Chang; Kui Zhang; Ting Xu; Ji Li; Xia Liang; Yuhang Xu; Long D. Nghiem; M.A.H. Johir; Yuquan Wei (Bioresource Technology, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Research progress on triterpenoids in the genus Rubus : a comprehensive review - Xi-Ya Li; Ting-Cai Dong; Yong-Fan Zi; Yan Luo; Yuan Li; Rui-Feng Mei; Le Cai (Natural Product Research, 2026)

Design, synthesis and activity evaluation of usnic acid monoesterification derivatives - Qing Zhang; Jun-Li He; Xiao-Xia Zhuo; Yi-Meng Hao; Hong-Ting Duan; Yan Jia; Jing-Jing Wang; Li-Ning Wang (Natural Product Research, 2026)

Toxicity evaluation of fosthiazate to Bombyx mori Linnaeus (Lepidoptera: Bombycidae): A new perspective from the chirality - Yuepeng Qiu; Jiyan Hu; Yao Feng; Yan Ma; Chang Li; Yazhu Liu; Yonghong Lai; Changcai Wu; Ruilong Sun; Ting Tang; Lianshan Li; Fengsong Liu (Pesticide Biochemistry and Physiology, 2026)

Immunosuppressive spirocyclic labdane diterpenoids from Holocheila longipedunculata - Xiu-Ying Bai; Shu-Xi Jing; Ting-Ting Zhou; Yu Zheng; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Rational design of zeolite-based composite catalysts in catalytic cracking of polyethylene - Yan Li; Zhe Ma; Jingyuan Shang; Ting Wang; Xingong Zhang; Peng Xu; Chenzhao Wang; Xiang Feng; De Chen; Chaohe Yang; Xiaobo Chen (Fuel, 2026)

Decorating the bridge in through-space charge-transfer emitter with an electron-withdrawing group for facile synthesis, tunable emission/transport property and improved electroluminescence performance - Yan Shu; Dajun Zhuang; Ting Li; Zetian Wang; Yongjun Song; Lei He (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Florfenicol impairs photosynthesis and triggers oxidative stress in Phaeodactylum tricornutum: Physiological and transcriptomic evidence - Huan Yang; Dong-Sheng Zhao; Yu-Ting Chen; Nan Li; Xiufeng Yan; Hui-Xi Zou (Aquatic Toxicology, 2026)

Transcriptomic and physiological insights into Diethylstilbestrol toxicity in Phaeodactylum tricornutum - Dong-Sheng Zhao; Xiao-Li Liu; Yu-Ting Chen; Huan Yang; Muhammad Ahsan Farooq; Xiufeng Yan; Hui-Xi Zou (Aquatic Toxicology, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

Isovitexin accelerates diabetic wound repair via coordinated angiogenesis and collagen remodeling: Mechanistic insights from cellular and streptozotocin-induced SD rat models - Ting-ting Chen; Li-qin Xu; Zhi-gang Gao; Wei-wei Zhou; Yan Ying (Tissue and Cell, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Impacts of arsenic exposure through drinking water on pigment disorders: A meta-analysis and a Bayesian benchmark concentration analysis - Rujin Wang; Xingrun Li; Yuanjie Wei; Tingxu Jin; Yuanhui Zhu; Ting Zhang; Rui Yan; Heran Li; Koichi Kato; Runa A; Qianlei Yang; Yan An (Journal of Trace Elements in Medicine and Biology, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

An integrated Pb isotope-PMF framework for enhanced source apportionment and risk control of heavy metals in soils of a pyrite mining area - Shuai Yan; Mengjing Ni; Kunyu Li; Fei Wei; Qiuyu Huang; Yongxia Jia; Xiaojing Liu; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Shirong Zhang; Ting Li (Journal of Environmental Chemical Engineering, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Non-ionic microemulsion extraction and in situ cloud point liquid-liquid microextraction of flavonoids and carotenoids from functional food - Qian-Xue Shen; Yan-Hua Jiao; Ting-Hong Fei; Jun Cao; Li-Hong Ye (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Salt-resistant fluoride remediation using bioinspired metal–polymer framework - Fengzhen Liu; Jingkang Wang; Hongxun Hao; Yaowen Zhong; Yan Li; Na Wang; Ting Wang; Xin Huang (Chemical Engineering Journal, 2025)

Root-associated microbes drive caffeine mineralization for water pollution control - Yan Chen; Yandao Chen; Nan Zheng; Enguang Nie; Xilin Wang; Ting Chen; Zhiyang Yu; Sufen Zhang; Zhen Yang; Haiyan Wang; Qing X. Li (Chemical Engineering Journal, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Proteomics revealed the underlying mechanism of STAT1-induced cognitive deficits in 2-month-old C57 mice - Xiao Li; Ting Li; Bocheng Xiong; Juan Luo; Xifei Yang; Yan Feng (Experimental Brain Research, 2025)

Comparison of Muscle Texture Characteristics and Nutritional Composition Between Gene-Edited Intermuscular-Bone-Free Crucian Carp and Other Varieties - Huijie Zhou; Zhipeng Sun; Tan Zhang; Tingting Zhang; Ting Yan; Huan Xu; Mingliang Wei; Yashan Yin; Na Li; Youyi Kuang; Guangxiang Tong (Fishes, 2025)
The intermuscular-bone-free crucian carp (Carassius auratus, WUCI), developed through CRISPR/Cas9-mediated bmp6a and bmp6b knockout, offers advantages in consumer acceptance and processing efficiency. However, its effects on muscle texture and nutritional quality have not been fully elucidated. In this study, we compared the F3 generation of WUCI with its sibling wild-type crucian carp (Carassius auratus, WT), Songpu silver crucian carp (Carassius gibelio var. Songpu, SPYJ), and Fangzheng silver crucian carp (Carassius gibelio var. Fangzheng, FZYJ), focusing on muscle texture characteristics and nutritional attributes. WUCI exhibited significantly higher shear force but lower hardness than most comparison groups, with no substantial differences in muscle fiber morphology. Amino acid profiles were similar among all groups. WUCI showed lower crude fat content than WT but higher than FZYJ, and comparable levels of polyunsaturated fatty acids (PUFA), n-3 fatty acids, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) to WT and SPYJ. These findings indicate that the knockout of bmp6a and bmp6b does not alter muscle mass in crucian carp, supporting the potential of WUCI for commercial adoption as a gene-edited consumer-oriented fish product.

Aeromagnetic characteristics and lithologic mapping in Panzhihua-Anyi area - Jiao-jiao Li; Yong-jun Zhang; Yi-yuan He; Ting-yan Zhao; Shi-jun Li (Applied Geophysics, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Overexpression of G protein-coupled receptors (GPCRs) contributing to lambda-cyhalothrin resistance in Cydia pomonella - Yu-Xi Liu; Chao Hu; Zi-Nan Xia; Yan Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Jia Li; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Response of invasive Solidago canadensis to foliar application of natural herbicide and glyphosate - Muhammad Anas; Zhi-Yun Huang; HuAnHe Xiong; Muhammad Imran; Meng-Ting Yan; Qaiser Javed; Guang-Qian Ren; Shan-Shan Qi; Jian Li; Zhi-Cong Dai; Dao-Lin Du (Journal of Environmental Management, 2025)

Engineered Plasmonic multi-hot spots on magnetic Nanospheres for quantitative detection of pesticide residues on food surfaces via SERS tagging analysis - Ming-Jie Wan; Yu-Ting Wu; Yan-Hui Wang; Xiao-Hang Wu; En-Ming You; An Wang; Sheng-Hong Liu; Jin-Chao Chen; Yue-Jiao Zhang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

A protein structure-dependent fluorescent probe for real-time β-lactoglobulin detection - Xian-Ting Yan; Wen-Xuan Qin; Kai-Li Chang; Hong-Kai Bian; Xin-Yu Pan; Xiang Ding; Wen-Bo Liu; Qing Wang (Food Chemistry, 2025)

The effect and mechanism of NCOA4-mediated ferritinophagy in aluminum-induced ferroptosis of PC12 cells - Ruifeng Liang; Jiafen Zhang; Yan Luo; Yizhe Yang; Ting Zhou; Siyi Li; Jiawei Liu; Bingbing Zhang; Qiao Niu; Hongmei Zhang; Xiaojiang Qin; Junhong Gao (Food and Chemical Toxicology, 2025)

Robust fluorine-free static/dynamic anti-icing and photothermal de-icing superhydrophobic surface with multi-bioinspired structures and wettability - Wenliang Zhang; Dongsong Wei; Yafei Shi; Ting Lu; Zhen Zhang; Yuanpeng Wang; Shuyi Li; Ana Sofia Oliveira Henriques Moita; Zhiwu Han; Yan Liu (Chemical Engineering Journal, 2025)

Hydrogel-based bimodal sensor array via modular assembly with decoupled strain–temperature sensing and high sensitivity - Fei Wang; Xiaojing Wu; Wenao Liao; Ting Li; Yidan Hu; Yan Zhu; Chang Lu; Junwei Feng; Xilin Liu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Adsorption of copper and nickel by a stannum-functionalized 3D graphene composite: Synthesis, characterization and optimization studies - Nicholas Yung Li Loh; Wan Ting Tee; Yuanyuan Shao; Billie Yan Zhang Hiew; Suchithra Thangalazhy-Gopakumar; Suyin Gan; Lai Yee Lee (Process Safety and Environmental Protection, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Earthworm-assisted shift and enrichment of the active di(2-ethylhexyl) phthalate degraders in farmland soils by DNA-stable isotope probing - Ting Wei; Zhen Zhen; Shuwen Luo; Yijie Chen; Jin Li; Yan-Qiu Liang; Mengke Song; Jincheng Li; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Highly efficient stabilization of arsenic in the contaminated sediments of Jiehe River by schwertmannite to inhibit arsenic release into overlying water - Weichen Luo; Ting Li; Yan Dong; Yujun Zhou; Zhaodi Wu; Xuan Liu; Jiahao Ni; Jingang Xu; Dejin Zhang; Mingjiang Zhang; Di Fang; Lixiang Zhou (Journal of Hazardous Materials, 2025)

Acid-resistant ZrO2/PPy nanocomposite for efficient fluoride removal from hydrochloric acid - Yan Li; Xin Huang; Fengzheng Liu; Sanli Yin; Zijian Zhou; Bin Lu; Ting Wang; Na Wang; Hongxun Hao (Journal of Environmental Chemical Engineering, 2025)

The investigation of phosphonate-decorated covalent organic frameworks with photo responsive effect for the effective adsorption and separation towards rare earth elements - Runhan Yan; Hongmin Cui; Jingsong Shi; Wei Jiang; Fei Gao; Nanfu Yan; Yaqing Weng; Minghui Li; Yuewei Liu; Ting Cheng (Journal of Environmental Chemical Engineering, 2025)

A multi-sensor, phenology-based approach framework for mapping cassava cultivation dynamics and intercropping in highly fragmented agricultural landscapes - Xincheng Wang; Qinfei Wang; Hongyan Lai; Zhenwen Zhang; Ting Yun; Xiaojing Lu; Guizhen Wang; Shangye Lao; Qi Liao; Saiqing Lu; Ruirui Chen; Shijing Fang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Regulating electrostatic microenvironments in robust ultramicroporous metal-organic framework for promoting direct ethylene purification from ternary mixtures - Qiang Zhang; Wenxuan Feng; Yi-Long Li; Lan Lan; Yan-Ting Li; Lu-Lu Wang; Xiaolin Yu; Tong-Liang Hu (Chemical Engineering Journal, 2025)

Preparation of N-doped porous biochar with high CO2 adsorption performance via one-step molten salt thermal treatment - Tian Xie; Jing He; Liang-Chen Xu; Ting Yan; Quan-Wen Pan; Li-Wei Wang; Wei-Guo Pan (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

ChpR-displaying bacteria for bioremediation of chlorpyrifos and TCP: A whole-cell biosorbent approach - Yan Guo; Can Wu; Shun-yu Hu; Yu-xuan Xie; Wan-yan Wu; Bo-xin Li; Yu-ting Chen; Chang-ye Hui (Water Research, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Upstream moisture sources and circulation patterns controls Asian monsoon hydroclimate over the past 20,000 years - Jian Zhang; Ming-Qiang Liang; Jun-Yun Li; Yao Wu; Yan-Xia Xue; Wen-Jun Sun; Xiang-Zhuo Liu; Jin-Ke Chen; Chao-Jun Chen; Ting-Yong Li (Quaternary Science Reviews, 2025)

Glycerol enhanced simultaneous selenite bioremediation and astaxanthin biosynthesis in Haematococcus lacustris - Yu-Hu Jiao; Zhong-Hong Zhang; Yu-Hong Liu; Yan Huang; Meng-Ting Jiang; Yong-Teng Zhao; Xinfei Xie; Wei-Dong Yang; Hong-Ye Li; Lei Cui; Xiang Wang (Journal of Hazardous Materials, 2025)

Switching low-temperature CO2 hydrogenation product selectivity over metal–organic framework derived Co-based catalyst - Yan-Ting Li; Ying-Fei Huo; Yun-Yan Zhong; Lei Zhou; Min Feng; Tong-Liang Hu (Fuel, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

An injectable carrier-free and self-assembling nanofiber hydrogel with anti-inflammatory and spatiotemporally-controllable anti-VEGF releasing capability for treatment of choroidal neovascularization - Yanghui Xiu; Hui Yuan; Yuanrong Fan; Yu Su; Yujie Zhang; Yuan Xu; Sijie Zhao; Ziqing Gao; Ting Hu; Yan Qiu; Jia-Min Lu; Yuhang Li (Chemical Engineering Journal, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

Identifying Immune Response Protein Biomarkers in Parkinson’s-Related Cognitive Impairment and Depression - Qiaozhen Su; Ting Lu; Yan Xu; Zhe Li; Hongfeng Liang; Chunye Zheng; Kunhong Li; Linshuang Ye; Zhixuan Ren; Dafeng Hu; Yan Huang; Lihua Zhu; et al. (Molecular Neurobiology, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Andrograpalides A–N, structurally diverse ent-labdane diterpenoids with anti-inflammatory activities from the leaves of Andrographis paniculata - Xiao Zhang; Yan-Zhen Li; Ya-Ting Lai; Wei Zeng; Min Yu; Jun-Tao Huang; Hong-Lei Jin; Wei-Qun Yang; Zhong-Xiang Zhao (Phytochemistry, 2025)

Uptake, subcellular accumulation and metabolism of 14C-bisphenol S in flowering cabbage - Yandao Chen; Yan Chen; Sihan Yao; Xilin Wang; Ting Chen; Kai Chen; Juying Li; Changfeng Yin; Qingfu Ye; Haiyan Wang (Journal of Hazardous Materials, 2025)

Two magmatic-hydrothermal events in Xinzhai Sn polymetallic deposit, Yunnan Province, China: Constraints from cassiterite U-Pb geochronology and elemental compositions of single fluid inclusions - Ying-Hua Chen; Wen-Chang Li; Ting-Guang Lan; Xiao-Yu Zhao; Ming-Guo Deng; Die Wang; Yan-Wen Tang; Ji-Huang Lai (Gondwana Research, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Impact of ectomycorrhizal symbiosis on root system architecture and nutrient absorption in Chinese chestnut and pecan seedlings - Ting Chen; Cancan Zhu; Shucheng Li; Yan Xia; Jian Huang; Wu Wang; Chunlan Lian; Yu Chen; Yuqiang Zhao; Shijie Zhang (Plant and Soil, 2025)

Six Weeks of Moderate-Intensity Treadmill Exercise Improves Intestinal Barrier and Intestinal Inflammation in Parkinson’s Disease Mice - Ting Li; Sheng-Yang Zhou; Wei Quan; Yu Zhou; Jian Wu; Li-Ping Zhao; Chen-Meng Qiao; Wei-Jiang Zhao; Chun Cui; Yan-Qin Shen (Molecular Neurobiology, 2025)

Nuclear magnetic resonance-based metabolomic study of rat brain after different intensity treadmill running - Ni Zeng; Jie-Ting Li; Zhi-Juan Zhang; Zhi-Peng Yan; Tao Liao; Guo-Xin Ni (Journal of Physiology and Biochemistry, 2025)
Previous studies have revealed that different intensities of exercise training have an impact on cognition. However, the cognitive effects of different intensities of exercise and its underlying mechanisms are not fully understood. The aim of this paper was to investigate the effects of different intensities of treadmill exercise on cognition in rats from the perspective of metabolomic analysis. In this study, ninety-six male rats were randomly divided into four groups: control group (CON group, n = 24), low-intensity running group (LIR group, n = 24), medium-intensity running group (MIR group, n = 24), and high-intensity running group (HIR group, n = 24). After 4 weeks of treadmill running, rats in the LIR group located the platform significantly faster than those in the CON( p = 0.027) and HIR( p = 0.011) groups. After 8 weeks of treadmill running, rats in the LIR and MIR groups also found the platform more quickly than those in CON group ( p = 0.003 and p = 0.015, respectively). Additionally, rats in the MIR group showed significantly increased superoxide dismutase (SOD)/catalase (CAT) in the hippocampus compared with those exposed to HIR( p = 0.03), LIR( p = 0.0008), and CON( p = 0.0004). Metabolomic analysis revealed that, after 8 weeks of running, 14 metabolites with similar characteristics differed between the MIR and HIR groups compared to the CON group. The LIR group showed significant alterations in 12 key metabolites compared to the CON group. The LIR, MIR, and HIR groups also demonstrated significant changes in 3, 4, and 3 metabolic pathways respectively, when compared to the CON group. In conclusion, the above results indicate that LIR can effectively decrease fumarate accumulation, thereby enhancing the TCA cycle and brain energy metabolism which in turn improved cognitive function, while MIR can modify glutathione metabolism to alleviate oxidative stress (OS), supporting cognitive function.

NLRP3-Mediated PANoptosis and Associated Interventions in Endothelial Injury - Aiwei Yan; Ting Cao; Xiao Li; Xingchen Li; Chaochu Cui; Xianwei Wang (Cardiovascular Toxicology, 2025)

Comparative transcriptome analysis of head kidney and gill with infection of spring viremia of carp virus in common carp (Cyprinus carpio) - Cuixia Wang; Yingying Zhang; Dongchun Yan; Lingjun Si; Linrui Chang; Ting Li (Aquaculture, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Microbial taxonomic diversity and functional genes mirror soil ecosystem multifunctionality in nonferrous metal mining areas - Meng-yao Zheng; Xiao-jun Qi; Zhi-yue Liu; Yi-ting Wang; Yan-bo Ren; Yuan Li; Yue Zhang; Bao-feng Chai; Tong Jia (Journal of Hazardous Materials, 2025)

Ni-modified 3D porous carbon materials for upgrading coal pyrolysis volatiles to improve tar quality and inhibit coke formation - Qian Wang; Ting Li; Qian Tian; Nichen Wang; Yanfeng Shen; Lunjing Yan; Meijun Wang; Liping Chang; Weiren Bao (Fuel, 2025)

Effects of L-arginine supplementation on fat deposition and meat quality in growing lambs: Interactions with gut microbiota and metabolic signalling pathways - Letian Kang; Xuan Li; Xin Zhao; Ting Liu; Ye Jin; Yan Duan (Food Chemistry, 2025)

Solar-driven Mn-Co3O4/NF dual-function evaporator integrating hydrovoltaic–galvanic effects for enhanced desalination and power generation - Ziyi Wang; Yuqian Zhang; Chengping Li; Liang Wang; Ting Bian; Shitan Yan; Kuzmin Anton; Liuting Zhang (Chemical Engineering Journal, 2025)

Collagen targeting BMSCs-derived extracellular vesicles coupled with decellularized tendon scaffold for anterior cruciate ligament reconstruction - Jie Wang; Jing Cui; Liang-Ju Ning; Yan-Jing Zhang; Fei Xing; Lei-Lei Zhao; Hui-Min Liu; Xuan Li; Min Zhu; Jing-Cong Luo; Zhou Xiang; Ting-Wu Qin (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Effects of Maternal Trace Elements Exposure in Early Pregnancy on Maternal Thyroid Hormones and Birth Outcomes - Ting Wu; Tao Li; Chen Zhang; Yan-Hui Hao; Si-Wei Zhang; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Biological Trace Element Research, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Point-by-point data-driven approach for statistical downscaling of integrated wave parameters in coastal regions - Ting Du; Hao Qin; Yan Li; Haoyu Jiang (Ocean Engineering, 2025)

Designing flexible aliphatic linker based molecular imprinted covalent organic framework for rapid and selective extraction and detection of trace zearalenone - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Grafting geminized amphiphilic polymer brushes on bioinspired hierarchical structured surface for super-bactericidal and fouling-release performances - Ting Chen; Mengbin Xin; Ziqin Yi; Yan Xiongjian; Xie Yixing; Li Linmei; Chongxiong Duan; Minghui Zhang; Akbar Halimov (Journal of Environmental Chemical Engineering, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Microbial communities and metabolite dynamics in the flowering fermentation of Fu brick Tea: Correlations with mycotoxin degradation - Yike Han; Xingnan Wang; Hongcai Li; Yuanye Liu; Mengzhen Han; Yanting Chen; Jingyi Ren; Ting Liu; Yan Liang; Xin Hu; Guimei Chen; Chunfeng Guo; et al. (Food Bioscience, 2025)

Highland barley functional tea extract alleviates alcoholic liver disease by modulating gut microbiota and reducing hepatic oxidative stress and inflammation in mice - Juan Li; Zhaozhan Liu; Yan Du; Zhiming Zhong; Zhaoxin Tu; Wenju Zhou; Zhengxing Chen; Li Wang; Xinxia Zhang; Ting Li (Food Bioscience, 2025)

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Physiological, transcriptomic and metabolomic responses of the marine diatom Phaeodactylum tricornutum to the auxin IAA - Yu-Ting Chen; Dong-Sheng Zhao; Xiao-Li Liu; Huan Yang; Run-Ze Gu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Algal Research, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Study on the improvement of Rye bread quality by bacterial Laccase derived from Streptomyces coelicolor - Ran Zhang; Yanhua Li; Yuan Gao; Fengyun Wang; Peng Zhou; Yan Zhang; Ying Li; Kaiyue Wang; Ting Rui; Guilan Zhu; Jingjing Wang; Zemin Fang (Journal of Cereal Science, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Catalytic upgrading of tar by regulating reactions of coal pyrolysis volatiles over acid-base bifunctional carbon-based composites - Qian Wang; Ting Li; Qian Tian; Nichen Wang; Meijun Wang; Yanfeng Shen; Lunjing Yan; Jiao Kong; Liping Chang; Weiren Bao (Fuel, 2025)

Antioxidant and antimicrobial PSE-like chicken protein isolate films loaded with oregano essential oil nanoemulsion for pork preservation - Chen-Yan Zhu; Ke Li; Yu Wang; Man-Ting Du; Bo Chen; Yun-Tao Wang; Yan-Fang Zhou; Yan-Hong Bai (Food Chemistry, 2025)

Long-term intercropping regulates the community structure of arbuscular mycorrhizal fungi and improves wheat yield - Binzhi Wang; Bijie Hu; Ting Li; Yan Dong (Field Crops Research, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

The light-responsive transcription factor SlBBX20 improves low-temperature resistance of Solanum lycopersicum by affecting photosynthetic capacity, antioxidant capacity, and osmotic adjustment - Yongbo Ma; Manling Chen; Yingjin Xing; Zhenglun Li; Ting Zhou; Haijing Yan; Jiahui Yan; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Plant Cell Reports, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

Disrupted coordination between primary and high-order cognitive networks in Parkinson’s disease based on morphological and functional analysis - Yunxiao Ma; Li Wang; Ting Li; Jian Zhang; Shintaro Funahashi; Jinglong Wu; Xiu Wang; Kai Zhang; Tiantian Liu; Tianyi Yan (Brain Structure and Function, 2025)

A feasibility study on cortisol and cortisone as biomarkers for psychological stress in wastewater-based epidemiology - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Jian-Guo Lin; De-Gao Wang (Water Research, 2025)

Down-regulation of platelet-derived growth factor receptor β in pericytes increases blood-brain barrier permeability and significantly enhances α-synuclein in a Parkinson’s Disease 3D cell model in vitro under hyperglycemic condition - Ting Wang; Meng-yan Li; Zhong Pei; Qiu-Xia Chen; Qiu-sheng Cheng; Ze Li (Tissue and Cell, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Sugar and anthocyanins: A scientific exploration of sweet signals and natural pigments - Ting Zhao; Qian Li; Ting Yan; Boping Yu; Qi Wang; Delu Wang (Plant Science, 2025)

Odor impact patterns and health risks of various enterprises in the rubber product manufacturing industry - Yan Zhang; Yan Zhao; Li’an Hou; Zhiyang Zhang; Kehua Zou; Gen Wang; Zhiqiang Lu; Huanwen Cui; Jie Meng; Ting Wu; Jing Wang; Zengxiu Zhai (Journal of Hazardous Materials, 2025)

Application of microfluidics for revealing physiological metabolic response of algae at the single-cell level - Yu-Fen Qiao; Song-Ya Li; Ting-Ting Liu; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Chemical Engineering, 2025)

Gelling properties and formation mechanism of blueberry pomace polysaccharide gels induced by calcium ions - Yuanfei Ge; Yan Zhang; Ting Peng; Liuqing Yang; Xiaomin Li; Chuyan Wang (Food Chemistry, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Survival and growth of stump sprouts in canopy gaps: A seven-year study in a temperate secondary forest - Ting Zhang; Qiaoling Yan; G. Geoff Wang; Shuangtian Li; Lizhong Yu; Jiaojun Zhu (Forest Ecology and Management, 2025)

Enhancement of gel characteristics of curdlan thermo-irreversible gels by β-cyclodextrin and its possible mechanisms - Ting-Ting Chen; Donghong Liu; Long-Qing Li; Ming-Yu Jin; Ya-Hui Yu; Jing-Kun Yan (Food Chemistry, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Antibiotic resistance genes in the coastal atmosphere under varied weather conditions: Distribution, influencing factors, and transmission mechanisms - Ting Zhang; Lingchong Yan; Jianhua Qi; Rongguo Su; Xianguo Li; Shaohua Sun; Yongzhong Song; Mingming Wei; Dahai Zhang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Sublethal effects of lambda-cyhalothrin on the biological characteristics, detoxification enzymes, and genes of the papaya mealybug, Paracoccus marginatus - Jian-Yu Li; Yan-Ting Chen; Yan Chen; Jian-Wei Zhao; Jian-Wei Fu; Meng-Zhu Shi (Journal of Pest Science, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

Double enzyme enhanced microbial induction of carbonate precipitation (E-MICP) to improve mechanical properties of sandy soil and its biocementation mechanism - Lei Niu; Yao-ting Duan; Xin Xu; Xiao-yan Wu; Zhe Wang; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2025)

Characterization of non-typhoidal Salmonella reveals the highly prevalent mcr-1-positive S. 1,4,[5],12:i:- within eggs are derived from chickens - Ting-Yu Yang; Tiantian Liu; Yan Li; Zeqing Wang; Meijun Chu; Junjie Wang; Ming Zou; Bao-Tao Liu (International Journal of Food Microbiology, 2025)

Evolution of the Asian summer monsoon during the Heinrich events 1–6 - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Jun-Yun Li; Hai Cheng; Chuan-Chou Shen; Jian Zhang; Ting-Yong Li (Global and Planetary Change, 2025)

Formation and evolution of coke of pyrolytic volatiles of low-rank coal on the carbon-based catalysts - Qian Wang; Ting Li; Yanfeng Shen; Lunjing Yan; Wei Xie; Meijun Wang; Liping Chang; Weiren Bao (Fuel, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Corrigendum to “Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride” [Chem. Eng. J. 474 (2023) 145508] - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2025)

Leaching kinetics combined with DFT simulation to explore the mechanism of differential phase transformation of calcium in magnesium slag induced by HCl and the preparation of calcium carbonate by electrolytic carbonization - Ren-yun Zhang; Yan Liu; Zhi-yu Fan; Ji-dong Li; Yi-yong Wang; Ting-an Zhang; Hong-xuan Xing; Yi-feng Liu; Xue-qiang Gong (Chemical Engineering Journal, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

A case study from a critical stopover site in the East Asian-Australasian Flyway provides lessons for optimal high-tide roost management to support shorebird conservation - Jia Guo; Waner Liang; Yan Zhou; Yifei Jia; Hongyan Yang; Lili Sun; Qing Chen; Ting Fu; Sicheng Ren; Wenkui Jiang; Guangchun Lei; Li Wen (Biological Conservation, 2025)

Simulating Sugarcane Elongation by a Multi-Parameter Generalized Logistic Model with Meteorological Effect - Guojun Zheng; Pengcheng Ma; Qinlong Wang; Hairong Huang; Ting Luo; Xiang Li; Meixin Yan; Zeping Wang; Guanghu Zhu (Sugar Tech, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Effects of Enterocytozoon hepatopenaei infection on intestinal immune defense and physiological processes of Penaeus vannamei - Zheng Cao; Chuanyu He; Zhipeng Yin; Caiyi Chen; Fan Li; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Frontiers in Marine Science, 2025)
As the main pathogen causing growth retardation, EHP is considered to be mainly parasitic in the hepatopancreas of shrimp. However, the intestines of shrimp infected with EHP frequently exhibit syndromes such as jejunum and white midgut. Therefore, the challenge experiment was carried out in this study to compare the differences in intestinal histology, digestion and absorption, immune defense and oxidative stress of P. vannamei between the control group and EHP infection group. Histological analysis showed that EHP infection significantly damaged the intestine of the shrimp, including intestinal villus rupture and outer membrane impairment. Concurrently, EHP infection can trigger intestinal immune response, and the expression of key immune genes like Toll, myeloid differentiation factor, anti-lipopolysaccharide factor, and Relish was significantly enhanced, while the expression of IMD and alkaline phosphatase was suppressed. Additionally, antioxidant genes manganese superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, and nuclear factor E2-related factor 2 were up-regulated to varying extents in EHP infection group, and the contents of lipid peroxides and malondialdehyde were heavily accumulated. Moreover, the expression levels of key genes involved in nutrient absorption, transport and synthesis, such as glucose transporter 1, Na + -K + ATPase, fatty acid synthase, acetyl-CoA carboxylase, rapamycin kinase, mTOR regulation-related protein, eukaryotic translation initiation factor 4E binding protein, ribosomal protein S6 kinase, were significantly up-regulated. However, the activities of amylase, lipase, and trypsin were inhibited in EHP infection group throughout the experiment. In summary, EHP infection damaged the intestine of P. vannamei , accompanied by immune response and oxidative stress. At the same time, nutrient transport and synthesis pathways were activated, while digestive enzyme activities were inhibited, indicating that in order to maintain survival, shrimps must accelerate material transport. Unfortunately, it remains in a state of nutrient deficiency that ultimately affects growth.

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Immunosuppressive leucosceptrane-type sesterterpenoids with antipodal cyclopentenones isolated from Leucosceptrum canum - Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Ting-Ting Zhou; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

N-methyladenosine on the natural antisense transcript of NIA1 stabilizes its mRNA to boost NO biosynthesis and modulate stomatal movement - Jie Li; Wen Tian; Ting Chen; Qing-Yan Liu; Hua-Wei Wu; Chuan-Hui Liu; Yuan-Yuan Fang; Hui-Shan Guo; Jian-Hua Zhao (Molecular Plant, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Exogenous additives reshape the microbiome and promote the reduction of resistome in co-composting of pig manure and mushroom residue - Li Zhang; Lan Jiang; Wenjing Yan; Hanxiang Tao; Chengcheng Yao; Lu An; Yifan Sun; Ting Hu; Wei Sun; Xun Qian; Jie Gu (Journal of Hazardous Materials, 2025)

Anchoring Cu on Zirconium-oxo nodes in a pore-confined metal-organic framework for CO2 hydrogenation to methanol - Chaosheng Bao; Ying-Fei Huo; Yan-Ting Li; Shan-Qing Yang; Wei Li; Tong-Liang Hu (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

Changes of bacterial necromass and their roles in humus conversion during organic wastes composting from different sources - Wenjie Chen; Yan Yang; Su Chang; Yuquan Wei; Zhen Wu; Kaiyan Tang; Yuan Chang; Yifan Zhang; Ji Li; Ting Xu; Xia Liang (Bioresource Technology, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Protein arginine methyltransferase 5 confers the resistance of triple-negative breast cancer to nanoparticle albumin-bound paclitaxel by enhancing autophagy through the dimethylation of ULK1 - Jing Kong; Yan Dong; Mengxuan Li; Jing Fan; Ting Wang (Toxicology and Applied Pharmacology, 2024)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Assessing the stability of terrestrial water storage to drought based on CMIP6 forcing scenarios - Wei Wei; Jiping Wang; Xufeng Wang; Yongze Song; Mohsen Sherif; Xiangyu Wang; Ashraf Dewan; Omri Y Ram; Peng Yan; Ting Liu; Dang Lu; Yongfan Guo; et al. (Journal of Hydrology, 2024)

Calixarene incorporated molecular imprinting on covalent organic framework for supramolecular recognition and specific extraction of citrinin - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Synergistically achieving particulate matter reduction and production performance optimization for zinc electrolysis by ultrasonication coupling anode-coated MnO2 - Yanhui Wang; Lingyu Li; Xiyu Jiang; Haiteng Zhang; Xiaocan Bai; Yuhan Huang; Ting Liu; Yan Tan; Zizhen Ma; Huawei Zhang (Journal of Environmental Chemical Engineering, 2024)

Comparative analysis of lipid composition in colostrum and mature milk from women of seven Chinese ethnic groups - Zhiyi Zhang; Teng Wei; Xinggang Ni; Ting Li; Ignatius Man-Yau Szeto; Sufang Duan; Yalu Yan; Wenhui Ye; Jing Li; Zeyuan Deng (International Dairy Journal, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Nature-inspired temperature-adaptive module: Achieving all-season passive thermal regulation for buildings - Lin Liang; Jianheng Chen; Kaixin Lin; Xueming Yang; Sai Liu; Chui Ting Kwok; Hao Pan; Ziai Liu; Aiqiang Pan; Siru Chen; Yihao Zhu; Wei Li; et al. (Energy and Buildings, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Synergistic effects of selenium and zinc on Bletilla striata (Thunb.) Reichb. F. growth and polysaccharide antioxidation - Changli Hu; Chengying Wang; Yan Wu; Long Liang; Liwei Yin; Xu Cheng; Conghu Li; Ting Hu (BioMetals, 2024)

Functional diversification of contact calls contribute to the cohesion of a multi-level society - Yi-Jun Yang; Ying Yan; Gu Fang; Yu-Ting Song; Jing Zang; Wen-Yong Tian; Dai-Bo Zhu; Paul A. Garber; Bao-Guo Li; Xiao-Guang Qi (Behavioral Ecology and Sociobiology, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Modeling the impact of long-term land use changes on deep soil hydrological processes in the Loess Plateau, China - Yakun Wang; Yanan Jiang; Ying Zhao; Xinbo Li; Kun Xie; Ting Yan; Tingting Wei; Ping Li; Huijie Li (Journal of Hydrology, 2024)

Efficient elimination of antibiotics and antibiotic resistance genes in hyperthermophilic sludge composting - Ting Pan; Yan-Yan Zhou; Qian Xiang; Xin-Li An; Qiang Pu; Jian-Qiang Su (Journal of Hazardous Materials, 2024)

Accumulation and metabolism of selenium in the rare yeast Kazachstania unispora during the selenium enrichment process - Furong Wang; Xiaoben Li; Xian Wang; Ivan Kurtovic; Min Yan; Jianping Wei; Ting Zhang; Xuejun Zeng; Yahong Yuan; Tianli Yue (Food Chemistry, 2024)

Emulsions stabilized by okra polysaccharides: Physicochemical, interfacial, and emulsification properties - Yue Lv; Xiujuan Cai; Ting Xv; Hongxu Gao; Yuan Xv; Yuchao Gu; Dan Cheng; Mingyan Yan; Yinping Li (Food Hydrocolloids, 2024)

Molecular characterization and functional analysis of ZAP-like gene in common carp (Cyprinus carpio) - Yingying Zhang; Cuixia Wang; Dongchun Yan; Lingjun Si; Linrui Chang; Ting Li (Fish & Shellfish Immunology, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

A fluorine-free bioinspired multifunctional slippery coating for ultra-long-term anticorrosion of Mg alloy, static/dynamic anti-icing, antibacterial and antifouling - Wenliang Zhang; Shuyi Li; Dongsong Wei; Yafei Shi; Ting Lu; Zhen Zhang; Zhiwu Han; Yan Liu (Chemical Engineering Journal, 2024)

Closed-loop recyclable wood-plastic composite as a sustainable alternative to wood: A solution for utilizing wood waste and promoting carbon sequestration - Shuang-Xi Hou; Chun-Yan Zhao; Wan-Ting Xiong; Jie Zhang; Mao-Qin Li; Guo-Qiang Tian; Gang Wu; Si-Chong Chen; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Lipoic acid-functionalized platycodin D nanocarrier improves mitochondrial dysfunction and reverses diabetes - Qiong Shen; Wen-Ting Wang; Qiao-Yue Xing; Yan Bai; Yan-Fei Li (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Acute toxicity of salicylic acid and its derivatives on the diatom Phaeodactylum tricornutum: Physico-Biochemical and transcriptomic insights - Dong-Sheng Zhao; Muhammad Ahsan Farooq; Min Li; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Aiqin Zhang; Xiufeng Yan; Hui-Xi Zou; Qiuying Pang (Aquatic Toxicology, 2024)

Lapidilactobacillus salsurivasis sp. nov., Secundilactobacillus muriivasis sp. nov., and Streptococcus parasalivarius sp. nov., isolated from Traditional Chinese Pickle - Ting-Yu Wang; Chun Yan Li; Hao Wang; Chun Tao Gu (Current Microbiology, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Multiscale characterization of surfactant-enhanced coal rock pore-fracture imbibition - Qiming Huang; Yuting Yan; Bo Yu; Gang Wang; Shimin Liu; Hao Xu; Ting Liu; Mingyang Li; Xu Feng (Process Safety and Environmental Protection, 2024)

HZrO2@PPy nanocomposite for effective fluoride removal from environmental water - Yan Li; Qin Wang; Fengzheng Liu; Zijian Zhou; Xin Huang; Na Wang; Ting Wang; Hongxun Hao (Journal of Environmental Chemical Engineering, 2024)

Ferroptosis promotes valproate-induced liver steatosis in vitro and in vivo - Xinrui Yan; Linfeng Ma; Xue Chen; Jing Ren; Yu Zhai; Ting Wu; Yu Song; Xiaojiao Li; Yingjie Guo (Food and Chemical Toxicology, 2024)

Sym4state.jl: An efficient computation package for magnetic materials - Guolin Wan; Yuhui Li; Ting Lai; Peixuan Li; Yongqian Zhu; Jingyu Yang; Yan-Fang Zhang; Jinbo Pan; Shixuan Du (Computer Physics Communications, 2024)

Recyclable UV shielding film with water vapor barrier and antimicrobial properties enabled by in situ polymerization of caffeic acid phenethyl ester - Yan Lyu; Jiongjiong Li; Fangmin Liang; Wencan Ma; Hongxia Liu; Cheng Huang; Jian Jiao; Ting Wu; Guigan Fang (Chemical Engineering Journal, 2024)

Efficacy of novel anticoagulants derived from tick saliva in preventing hypercoagulation among post-acute COVID-19 patients - Dan Liao; Aaron Wei Liang Li; Cinthia Wan Ting Phua; Cheryl Xue Pei Chuah; Xiao Xun Yang; Tammy Xin Tian Low; Matthew Benson; Shoumo Bhattacharya; R. Manjunatha Kini; Mark Yan Yee Chan; Cho Yeow Koh (Toxicon, 2024)

BpAFP, a Broussonetia papyrifera latex chitinase, exhibits a dual role in resisting to both Verticillium wilt disease and lepidopterous pests, Plutella xylostella and Prodenia litura - Xianbi Li; Dan Jin; Feifei Yi; Meng Tang; Siyi Wan; Yanhua Fan; Yuehua Xiao; Ting Liu; Hui Li; Jiancong Li; Mingliang Qiu; Yan Pei (Plant Science, 2024)

Immunosuppressive leucosesterterpane and penta-nor-leucosesterterpane sesterterpenoids from Leucosceptrum canum - Ting-Ting Zhou; Man-Wen Zhang; Yan-Chun Liu; Xiao-Nian Li; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Competition between discharge reaction and side reaction for anode's lithium during internal short circuit in lithium-ion batteries - Cong-jie Wang; Yan-li Zhu; Tao Zhang; Jun Tian; Fei Gao; Yong Zhao; Xin-ya Bu; Ting Quan (Journal of Cleaner Production, 2024)

Tuning the planarity of molecularly imprinted covalent organic frameworks for selective extraction of ochratoxin A in alcohol samples - Hao-Ze Li; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Food Chemistry, 2024)

Preparation of gelatin-starch shell-yolk microspheres by water-in-water emulsion method: Effects of starch crystal type and cross-linking - Zhirenyong Zhang; Xiaoxue He; Ting Yan; Yuyu He; Chaoxi Zeng; Shiyin Guo; Qingming Li; Huiping Xia (Food Hydrocolloids, 2024)

Sustained high expression of NRF2 inhibits cell apoptosis in arsenite-transformed human keratinocytes - Qianlei Yang; Ting Zhang; Jian Liu; Hui Lu; Chen Zhao; Chunchun Li; Koichi Kato; Dapeng Wang; Yan An (Food and Chemical Toxicology, 2024)

A novel nitric oxide-driven nanomotor for synergistic treatment of ischaemic stroke: Enhanced deep brain penetration and therapeutic efficacy - Zhicheng Xiao; Yi Li; Ting Chen; Chenchen Xie; Jun Liao; Pu Lin; Zhe-Sheng Chen; Yan Qiu; Jian Cai; Chuan Zhang; Tingfang Wang (Chemical Engineering Journal, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

The influence of hydrogeology and carbon sources on speleothem δ13C based on long-term monitoring in Furong Cave, southwest China - Jun-Yun Li; Ting-Yong Li; Hong-Chun Li; Christoph Spötl; Chao-Jun Chen; Jian Zhang; Yao Wu; Hua-Yan Li; Yue Jin; Min Zhao; Hong-Kai Li; Yan-Min Dong (Chemical Geology, 2024)

Research on heat dissipation optimization and energy conservation of supercapacitor energy storage tram - Yibo Deng; Sheng Zeng; Chushan Li; Ting Chen; Yan Deng (Waste Disposal & Sustainable Energy, 2024)

Potential failure mechanism of a rock slope with weak intercalated layer and the reinforcement effect evaluation - Hai-Ning Liu; Su-Zhen Duan; Ting-Song Yan; Han-Dong Liu; Dong-Dong Li (Natural Hazards, 2024)

Effects of Straw and Nitrogenous Fertilizers on the Soil Aggregate Stability and Quality in Subtropical Regions of China - Jia Yi Yang; Shahbaz Atta Tung; Jin Ting Xu; Yan Qiong Pan; Li Yang; Xun Bo Zhou (Journal of Soil Science and Plant Nutrition, 2024)

Prevention and control strategies for antibiotic resistance: from species to community level - Yan-Zi Wang; Hu Li; Qing-Lin Chen; Ting Pan; Yong-Guan Zhu; Dirk Springael; Jian-Qiang Su (Soil Ecology Letters, 2024)

Effects of GPS flex power on DCBs, ionospheric delays and positioning - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Yan Xiang; Wanqiang Yao; Ting Ma; Qin Li (Advances in Space Research, 2024)

Abundance and health risk of bioaerosols in the coastal areas of Qingdao, China - Lingchong Yan; Ting Zhang; Shaohua Sun; Yongzhong Song; Chen Han; Yao Wang; Jianhua Qi; Xianguo Li; Dahai Zhang (Aerobiologia, 2024)

First report of chilli veinal mottle virus infecting Lactuca sativa in China - Yue Chen; Gui Gao; Ting Ting Li; Jie Chen; Yue Yan Yin; Jing Zhong; Liling Zhao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2024)

Enhanced removal of lead and zinc by a 3D aluminium sulphate-functionalised graphene aerogel as an effective adsorption system - Nicholas Yung Li Loh; Wan Ting Tee; Svenja Hanson; Wee Siong Chiu; Billie Yan Zhang Hiew; Poi Sim Khiew; Lai Yee Lee (Chemosphere, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Preparation of β-cyclodextrin-reduced graphene oxide aerogel and its application for adsorption of herbicides - Ting Yao; Hong Chen; Yue Luo; Hui Li; Xiaolan Shao; Qianqi Zheng; Dingdi Tu; Bei Yan; Jinfeng Dai; Lianyang Bai; Kailin Liu (Journal of Cleaner Production, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Deep removal of COS by carbon aerogel in natural gas: Performance and regeneration on K2O-Cu/CA adsorbent at room temperature - Ting Liu; Shengnan Deng; Zishun Li; Xianhong Wang; Yuhan Huang; Yan Tan; Zizhen Ma; Huawei Zhang (Fuel, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

The role of DsbA and PepP genes in the environmental tolerance and virulence factors of Cronobacter sakazakii - Tong Jin; Liuxin Pang; Ting Yue; Lingling Niu; Tingting Li; Yujing Liang; Yunlong Zhang; Chunhong Yan; Baowei Yang; Chunling Zhang; Xiaodong Xia (Food Research International, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Effect of benzoic acid-based and cinnamic acid-based polyphenols on foaming properties of ovalbumin at acidic, neutral and alkaline pH conditions - Hedi Wen; Deju Zhang; Zhenzhen Ning; Zihao Li; Yan Zhang; Jingbo Liu; Ting Yu; Ting Zhang (Food Hydrocolloids, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Elucidating the role of polar functional groups in fluorinated polymer artificial interphase for stable lithium anodes - Kun Li; Zhen Wang; Borui Yang; Ting Li; Bin Li; Jiahao Chen; Zhongfu Yan; Miao He; Anjun Hu; Jianping Long (Chemical Engineering Journal, 2024)

HO-1 activation contributes to cadmium-induced ferroptosis in renal tubular epithelial cells via increasing the labile iron pool and promoting mitochondrial ROS generation - Yan-Ting Lv; Tian-Bin Liu; Yue Li; Zhen-Yong Wang; Cai-Yu Lian; Lin Wang (Chemico-Biological Interactions, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Systemic glucocorticoids link to long-term microvascular injury in COVID-19 - Qian Yang; Cai Yun Xia; Ying Cai; Yan Fang Zhang; Dao Ting Li; Shu Qi Wu; Peng Hu (Angiogenesis, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Cellulose-derived raw materials towards advanced functional transparent papers - Yanhua Guan; Li Yan; Hai Liu; Ting Xu; Jinghuan Chen; Jikun Xu; Lin Dai; Chuanling Si (Carbohydrate Polymers, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Soil microbial functional diversity is primarily affected by soil nitrogen, salinity and alkalinity in wetland ecosystem - Meng-Yuan Zhu; Zhen-Di Liu; Yan-Yu Song; Xian-Wei Wang; Jia-Bao Yuan; Meng-Ting Li; Yan-Jing Lou; Zhen-Ling Gao; Chang-Chun Song (Applied Soil Ecology, 2024)

Berberine hydrochloride delays citrus sour rot mainly by disrupting carbohydrate and energy metabolism of Geotrichum citri-aurantii spores - Lu Li; Bo Lin; Yu Ting; Maohui Li; Jinjin Hu; Jingjing Song; Yingjuan Yan; Jiaxin Chen; Hong Xiao; Nengguo Tao (Pesticide Biochemistry and Physiology, 2024)

Heating rate effects on the coking properties evolution for varying rank coals: Insights into volatiles reaction and mass transfer - Beibei Cui; Meijun Wang; Zhihong Li; Xin Jin; Yanfeng Shen; Ting Li; Lunjing Yan; Liping Chang (Fuel, 2024)

Insight into sodium selenite-induced metabolic reprogramming in response to main seleno-amino acid enrichment in Saccharomyces cerevisiae using metabolomics - Furong Wang; Min Yan; Ting Zhang; Zhen Tian; Xinxin Niu; Zimeng Guo; Xian Wang; Xiaoben Li; Wei Song; Yan'e Luo; Yahong Yuan; Tianli Yue (Food Bioscience, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

High capacity and long service in sodium-ion batteries achieved by the refinement of BiOCl from lamellar to flower-like in ether electrolyte - Sheng-Li Wei; Yan-Ling Yang; Xiao-Lei Shi; Yu Sun; Jin-Geng Chen; Xue-Feng Tian; Yuan-Ting Wu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Low-voltage stimulated denitrification performance of high-salinity wastewater using halotolerant microorganisms - Long Chen; Hai Xiang; Li-Ting Zhou; Yan-Qing Zhang; Yang-Cheng Ding; Di Wu; Nan-Wen Zhu; Yi-Feng Zhang; Hua-Jun Feng (Bioresource Technology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Evolutionary analysis of SLC10 family members and insights into function and expression regulation of lamprey NTCP - Yingying Zhu; Qipeng Zhang; Jilong Pan; Tiesong Li; Hao Wang; Jindi Liu; Lei Qian; Ting Zhu; Yue Pang; Qingwei Li; Yan Chi (Fish Physiology and Biochemistry, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Exploring of multi-functional umami peptides from Stropharia rugosoannulata: Saltiness-enhancing effect and mechanism, antioxidant activity and potential target sites - Wanchao Chen; Wen Li; Di Wu; Zhong Zhang; Zhengpeng Li; Long Li; Ting Wu; Yan Yang (Food Chemistry, 2024)

Phosphate additives promote humic acid carbon and nitrogen skeleton formation by regulating precursors and composting bacterial communities - Jing Su; Yabin Zhan; Yuan Chang; Su Chang; Yan Luo; Peizhen Chen; Xingling Tao; Yunfeng Chen; Li Yang; Ting Xu; Yuhui Qiao; Ji Li; et al. (Bioresource Technology, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

The alternation of flood and ebb tide induced arsenic release and migration from coastal tidal flat sediments in Yellow Sea wetlands: An ex-situ study - Ting Luo; Yan Sun; Weihao Liang; Qining Zheng; Sheng Kong; Lili Xue; Li Yan (Journal of Cleaner Production, 2024)

Caspase-8 dependent apoptosis contributes to dyskinesia caused by muscle defects and neurotoxicity in zebrafish exposed to zearalenone - Yunpeng Wang; Shuaiting Li; Zhi Cheng; Ziyuan Zhang; Yu Xu; Huan Zhang; Ting Xu; Jianqiang Chen; Danyang Yin; Wenhua Yan; Huizhe Huang (Food and Chemical Toxicology, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Effects of tree density variations on outdoor heritage conservation: Numerical study of an ancient brick city wall with four orientations - Ting Zhang; Changchang Xia; Yan Ma; Ruohan Zhang; Shuai Han; Zhenyi Kong; Shuichi Hokoi; Yonghui Li (Building and Environment, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

Characterization of multi-copy C3 genes and association analysis of C3.1 polymorphism with GCRV resistance traits in Ctenopharyngodon idella - Jia-yang Huang; Zhao Lv; Bin Li; Yan-rong Ying; Le Yang; Tiao-yi Xiao; Shu-ting Xiong (Aquaculture, 2024)

Effects of urbanization and topography on thermal comfort during a heat wave event: A case study of Fuzhou, China - Zefeng Zheng; Xinlu Lin; Li Chen; Chao Yan; Ting Sun (Sustainable Cities and Society, 2024)

Bioaerosols in the coastal region of Qingdao: Community diversity, impact factors and synergistic effect - Ting Zhang; Lingchong Yan; Mingming Wei; Rongguo Su; Jianhua Qi; Shaohua Sun; Yongzhong Song; Xianguo Li; Dahai Zhang (Science of The Total Environment, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Regulation of NF-κB signaling by NLRC (NLRC3-like) gene in the common carp (Cyprinus carpio) - Cuixia Wang; Jiahui Xu; Yingying Zhang; Dongchun Yan; Lingjun Si; Linrui Chang; Ting Li (Fish & Shellfish Immunology, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Regulation of secondary metabolites in the endophytic fungus Penicillium sp. KMU18029 by the chemical epigenetic modifier 5-azacitidine - Chang-Yan Li; Hong-Tao Li; Ya-Ting Shao; Xing-Yi Guo; Wei Li; Tian-Peng Yin (Natural Product Research, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Application of carboxymethyl cellulose sodium (CMCNa) in maize–wheat cropping system (MWCS) in coastal saline-alkali soil - Ge Li; Yuyang Shan; Weibo Nie; Yan Sun; Lijun Su; Weiyi Mu; Zhi Qu; Ting Yang; Quanjiu Wang (Science of The Total Environment, 2024)

Opportunities for converting waste plastics into petrochemicals: Process design, multi-objective optimization, and omnidirectional techno-economic-society-environment assessment - Xiaobo Chen; Jinqing Zhang; Zhibo Zhang; Zihao Zhang; Xin Zhou; Yaqi Zheng; Ting Wang; Guoliang Li; Ruzhen Ma; Qi Han; Hao Yan; Yibin Liu; et al. (Journal of Cleaner Production, 2024)

Novel modified semi-carbonized fiber prepared using discarded clothes for derisking Cu(II) and Pb(II) contaminated water - Hong-yan Deng; Yin-fei Wang; Meng-ting Guo; Wen-bin Li; Min Li; Chu-tong Yu (Journal of Environmental Management, 2024)

Nonlinear proinflammatory effect of short-term PM2.5 exposure: A potential role of lipopolysaccharide - Fangxia Shen; Mutong Niu; Haoxuan Chen; Ting Zhang; Jing Li; Haijie Tong; Yan Wu (Journal of Environmental Sciences, 2024)

Three-dimensional porous carbon materials as catalysts for upgrading coal pyrolysis volatiles to boost light tar - Qian Wang; Ting Li; Qian Liu; Yanfeng Shen; Lunjing Yan; Jiao Kong; Meijun Wang; Liping Chang; Weiren Bao (Fuel, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Demographic dynamics and molecular evolution of the rare and endangered subsect. Gerardianae of Pinus: insights from chloroplast genomes and mitochondrial DNA markers - Ting-Ting Zhang; Chun-Li Yan; Jin-Xia Qiao; Ao-Shuang Yang; Mi-Li Liu; Yi-Xuan Kou; Zhong-Hu Li (Planta, 2024)

Mapping liveability: The “15-min city” concept for car-dependent districts in Auckland, New Zealand - Jing Jiang; Weijie Qiao; I-Ting Chuang; Yan Li; Tianyi Wang; Lee Beattie (Applied Geography, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Quantitative SARS-CoV-2 exposure assessment for workers in wastewater treatment plants using Monte-Carlo simulation - Cheng Yan; Yi-ning Hu; Zi-cheng Gui; Tian-nuo Lai; Wajid Ali; Nian-hong Wan; Shan-shan He; Sai Liu; Xiang Li; Ting-xu Jin; Zaheer Ahmad Nasir; Sonia Garcia Alcega; et al. (Water Research, 2024)

Transgenerational effects of microplastics on Nrf2 signaling, GH/IGF, and HPI axis in marine medaka Oryzias melastigma under different salinities - Xiaolin Zhang; Xiao Chen; Lu Gao; Hai-Ting Zhang; Jiji Li; Yingying Ye; Qing-Ling Zhu; Jia-Lang Zheng; Xiaojun Yan (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Visible light-activated photosensitizer inhibits the plasmid-mediated horizontal gene transfer of antibiotic resistance genes - Yan-Zi Wang; Xin-Li An; Xiao-Ting Fan; Qiang Pu; Hu Li; Wen-Zhen Liu; Zhuo Chen; Jian-Qiang Su (Journal of Hazardous Materials, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Climatic factors and fertilization rates co-regulate anaerobic methane oxidation driven by multiple electron acceptors in Chinese paddy fields - Wang-ting Yang; Wei-qi Wang; Evgenios Agathokleous; Ya-nan Bai; Shuai Zhang; Chun Wang; Yan-fang Feng; Jia-qi Liu; Yu-ling Yang; Cai-yu Geng; Li-dong Shen (Journal of Cleaner Production, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

A bibliometric analysis of global research hotspots and progress on microplastics in soil‒plant systems - Pengxinyue Huang; Yanyan Zhang; Naseer Hussain; Ting Lan; Guangdeng Chen; Xiaoyan Tang; Ouping Deng; Chaorui Yan; Yang Li; Ling Luo; Wenyu Yang; Xuesong Gao (Environmental Pollution, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Plant Growth-Promoting and Arsenic Accumulation Reduction Effects of Two Endophytic Bacteria Isolated from Brassica napus - Wenying Chang; Xiping Hou; Yaoyao Yan; Ting Liu; Xianzhu Dai; Yasuo Igarashi; Li Fan; Caiyun Yang; Feng Luo (Journal of Plant Growth Regulation, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

Mitochondrial transplantation inhibits cholangiocarcinoma cells growth by balancing oxidative stress tolerance through PTEN/PI3K/AKT signaling pathway - Xiaocong Liu; Yuanyuan Zhang; Xiaoyan Yang; Yan Zhang; Yulan Liu; Li Wang; Ting Yi; Jing Yuan; Wu Wen; Yi Jian (Tissue and Cell, 2023)

CREB1 alleviates the apoptosis and potentiates the osteogenic differentiation of zoledronic acid-treated human periodontal ligament stem cells via up-regulating VEGF - Yao Duan; Chanyuan Jin; Yuwei Wu; Yan Chen; Minjuan Zhang; Jun Qian; Ting Shuai; Jian Li; Huimin Chen; Dan Li (Tissue and Cell, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Enhanced expression of RAGE/NADPH oxidase signaling pathway and increased level of oxidative stress in brains of rats with chronic fluorosis and the protective effects of blockers - Yan-Lin Ma; Jie Deng; Ting Zhang; Hong-Mei Li; Qiu-Zhe Liang; Kai-Lin Zhang (Journal of Trace Elements in Medicine and Biology, 2023)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Effects of GRP78 on endoplasmic reticulum stress and inflammation induced by Thapsigargin in macrophages of large yellow croaker (Larimichthys crocea) - Jie Sun; Qiuxin Yan; Zhihao Zhang; Ting Xu; Ye Gong; Weijia Li; Kangsen Mai; Qinghui Ai (Aquaculture, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

In situ growth of polydopamine modified ZIF-L arrays on air-laid paper as flexible evaporator for efficient solar desalination - Long Cheng; Linzhi Zuo; Shitan Yan; Jiubing Shen; Chengping Li; Yiting Che; Liang Wang; Romanov Anton; Ting Bian (Desalination, 2023)

Aeration intensity drives dissolved organic matter transformation and humification during composting by regulating the organics metabolic functions of microbiome - Ting Xie; Zhaohan Zhang; Yanling Yu; Yan Tian; Fei Wang; Dongyi Li; Jun Nan; Yujie Feng (Chemical Engineering Journal, 2023)

Improvement of Learning and Memory by Elevating Brain D-Aspartate in a Mouse Model of Fragile X Syndrome - Yu-Jiao Li; Kun Zhang; Ting Sun; Yan-Yan Guo; Qi Yang; Shui-Bing Liu; Yu-Mei Wu; Ming-Gao Zhao (Molecular Neurobiology, 2023)
Fragile X syndrome (FXS) is an inherited human mental retardation that arises from expansion of a CGG repeat in the Fmr1 gene, causing loss of the fragile X mental retardation protein (FMRP). It is reported that N-methyl-D-aspartate receptor (NMDAR)-mediated facilitation of long-term potentiation (LTP) and fear memory are impaired in Fmr1 knockout (KO) mice. In this study, biological, pharmacological, and electrophysiological techniques were performed to determine the roles of D-aspartate (D-Asp), a modulator of NMDAR, and its metabolizing enzyme D-aspartate oxidase (DDO) in Fmr1 KO mice. Levels of D-Asp were decreased in the medial prefrontal cortex (mPFC ); however, the levels of its metabolizing enzyme DDO were increased. Electrophysiological recordings indicated that oral drinking of D-Asp recovered LTP induction in mPFC from Fmr1 KO mice. Moreover, chronic oral administration of D-Asp reversed behavioral deficits of cognition and locomotor coordination in Fmr1 KO mice. The therapeutic action of D-Asp was partially through regulating functions of NMDARs and mGluR5/mTOR/4E-BP signaling pathways. In conclusion, supplement of D-Asp may benefit for synaptic plasticity and behaviors in Fmr1 KO mice and offer a potential therapeutic strategy for FXS.

In Silico and Expression Analysis of Papain-Like Cysteine Proteinases (PLCP) Genes in Vitis vinifera to Predict Their Involvement in Hormonal Signaling and Disease Resistance - Ting Zhao; Jing Yan; Ziyang Qu; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Journal of Plant Growth Regulation, 2023)

Insufficient SIRT1 in macrophages promotes oxidative stress and inflammation during scarring - Ting He; Xiaozhi Bai; Yan Li; Dongliang Zhang; Zhigang Xu; Xuekang Yang; Dahai Hu; Juntao Han (Journal of Molecular Medicine, 2023)

Water source identification in mines combining LIF technology and ResNet - Peng-cheng Yan; Yu-ting Zhao; Guo-dong Li; Jing-bao Wang; Wen-chang Wang (Journal of Mountain Science, 2023)

Long-term field translocation differentially affects arbuscular mycorrhizal and ectomycorrhizal trees in a sub-tropical forest - Ting Wu; David T Tissue; Wei Su; Xu Li; Shimin Yang; Xujun Liu; Yue Liu; Zhiyang Lie; Shuyidan Zhou; Ze Meng; Junhua Yan; Xuli Tang; et al. (Agricultural and Forest Meteorology, 2023)

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Three new compounds from Anoectochilus roxburghii (Wall.) Lindl - Yan-Lin Bin; Shun-Zhi Liu; Ting-Ting Xie; Wen-Zheng Feng; Hao-Yang Li; Zi-Jia Ye; Zhi-Hao Dong; Ying-Kun Qiu (Natural Product Research, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Carbon storage capacity of Castanopsis hystrix plantations at different stand–ages in South China - Xu Li; Luis Carlos Ramos Aguila; Jinchu Luo; Yue Liu; Ting Wu; Zhiyang Lie; Xujun Liu; Yan Cheng; Fen Jiang; Juxiu Liu (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Evaluation of adsorption performance and mechanisms of a highly effective 3D boron-doped graphene composite for amitriptyline pharmaceutical removal - Wan Ting Tee; Nicholas Yung Li Loh; Billie Yan Zhang Hiew; Pau Loke Show; Svenja Hanson; Suyin Gan; Lai Yee Lee (Journal of Environmental Management, 2023)

Detection of anthocyanin content in fresh Zijuan tea leaves based on hyperspectral imaging - Fushuang Dai; Jiang Shi; Chongshan Yang; Yang Li; Yan Zhao; Zhongyuan Liu; Ting An; Xiaoli Li; Peng Yan; Chunwang Dong (Food Control, 2023)

Effects of Fe and cost-effective media composition on arsenopyrite bioleaching by Sulfobacillus thermosulfidooxidans - Hong-Rui Chen; Duo-Rui Zhang; Xiao-Juan Zhao; Qian Li; Yu-Ting Liang; Eva Pakostova; Yan Zhang; Yong-Bin Yang (Chemical Engineering Journal, 2023)

Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2023)

Influence of cold atmospheric pressure plasma treatment of Spirulina platensis slurry over biomass characteristics - Zihan Li; Ting Zhou; Qi Zhang; Tongying Liu; Jiangling Lai; Canbo Wang; Leipeng Cao; Yuhuan Liu; Roger Ruan; Mingxiong Xue; Yunpu Wang; Xian Cui; et al. (Bioresource Technology, 2023)

Size-dependent chemical composition of atmospheric nanoparticles in urban Beijing during springtime - Yan Chen; Chenjuan Deng; Ting Lei; Junling Li; Chaofan Lian; Yiran Li; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Lei Li; et al. (Atmospheric Environment, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

Quantifying ant diversity and community in a subalpine forest mosaic: a comparison of two methods - Chuan-Jing Zhang; Yi-Ting Cheng; Xian-Shu Luo; Yao Chen; Yu-Chao He; Yan-Pang Li; Zhi-Pang Huang; Matthew B. Scott; Wen Xiao (Journal of Insect Conservation, 2023)
Sampling efficiency, composition and detection biases associated with pitfall-trap and sample plot (standardised hand-collecting) methods were compared at seven high montane sites at Lasha Mountain, Yunnan, China. Rarefaction-interpolation curves showed total species diversity and sample coverage from each method were undifferentiated. Permutational multivariate analysis of variance showed highly overlapping communities. However, of all species collected, just 53% of all species found were shared between the two methods; 30% were exclusive to sample plot samples and 17% were exclusive to pitfall traps. Modelled comparisons of species richness (alpha) and proportion of species from the population (beta diversity) showed differences between methods. Permutational multivariate analysis of variance blocked by site showed community composition differed between methods, defined largely by the presence of a few dominant species. Implications for insect conservation : Our findings suggest that results from the two methods cannot be directly compared and are imperfect substitutes to one another. For long-term monitoring of biodiversity in complex forest mosaic systems, we suggest integrating a suite of complementary methods to achieve more complete representation of ant composition and diversity.

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

Organic matter stabilization and phosphorus activation during vegetable waste composting: Multivariate and multiscale investigation - Tao Zhang; Huanhuan Li; Ting Yan; Sabry M. Shaheen; Yingqi Niu; Shiyu Xie; Yingyu Zhang; Hamada Abdelrahman; Esmat F. Ali; Nanthi S. Bolan; Jörg Rinklebe (Science of The Total Environment, 2023)

Identification of CCCH-type zinc finger antiviral protein 1 (ZAP) gene from Pacific white shrimp (Penaeus vannamei): Characterization and expression analysis in response to viral infection - Yingying Zhang; Jiahui Xu; Jiyue Yu; Lingjun Si; Linrui Chang; Ting Li; Dongchun Yan (Fish & Shellfish Immunology, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Ultrasound-driven nanoreactor with USP39 ShRNAi-intensified ferroptosis for synergistic sono-chemodynamic therapy - Zhiyu Zhao; Jiajing Liu; Yanjie Wu; Xiaochen Liang; Yijia Zhang; Tingting Li; Yunjie Wang; Yi Luo; Shengyu Wang; Gang Song; Ting Wu; Shaoliang Zhang; et al. (Chemical Engineering Journal, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Study of polycyclic aromatic hydrocarbons accumulation in bioretention facilities and its influence on microbial community structure - Ya-jiao Li; Yan-ting Shi; Ling-zhi Zhao; Ya-fang Li; Jia-ping Wang; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

High prevalence and genomic characteristics of carbapenem-resistant Enterobacteriaceae and colistin-resistant Enterobacteriaceae from large-scale rivers in China - Cai-Hong Guo; Yu-Qing Liu; Yan Li; Xiao-Xiao Duan; Ting-Yu Yang; Fang-Yu Li; Ming Zou; Bao-Tao Liu (Environmental Pollution, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Correction: Changes in soil phosphorus fractions following the conversion of Chinese fir plantations to evergreen broad-leaved forests in subtropical China - Junjie Lei; Yuanying Peng; Juan Cao; Rujie Li; Qiang Jia; Xiao Shi; Ting Zhou; Wende Yan; Xiaoyong Chen (European Journal of Forest Research, 2023)

Changes in soil phosphorus fractions following the conversion of Chinese fir plantations to evergreen broad-leaved forests in subtropical China - Junjie Lei; Yuanying Peng; Juan Cao; Rujie Li; Qiang Jia; Xiao Shi; Ting Zhou; Wende Yan; Xiaoyong Chen (European Journal of Forest Research, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Advanced oxidation-based combined conditioning technologies to improve sludge dewaterability: A mini review - Zhongqi He; Xu Zhou; Xiumin Fan; Wenbiao Jin; Chuan Chen; Bowen Yan; Shiyu Yin; Ting Zhou; Xuan Li; Guangming Jiang (Journal of Water Process Engineering, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

How do the hydroxyl group number and position of polyphenols affect the foaming properties of ovalbumin? - Hedi Wen; Deju Zhang; Zhenzhen Ning; Zihao Li; Yan Zhang; Jingbo Liu; Ting Zhang (Food Hydrocolloids, 2023)

Anaerobic-aerobic treatment of high-strength and recalcitrant textile dyeing effluents - Hai-Yong Yao; Hui Guo; Feng Shen; Ting Li; De-Yang Show; Ming Ling; Yue-Gen Yan; Kuan-Yeow Show; Duu-Jong Lee (Bioresource Technology, 2023)

Cell wall breaking of Haematococcus pluvialis biomass facilitated by Baijiu jiuqu fermentation with simultaneously production of beverages - Peng Zhang; Lan-Yi Lu; Shuang-Yan Liao; Gui-Ting Xu; Xin-Yi Liu; Zhang-Li Hu; Ying Xu; Li-Yan Wang (Bioresource Technology, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

VviKFB07 F-box E3 ubiquitin ligase promotes stilbene accumulation by ubiquitinating and degrading VviCHSs protein in grape - Ting Zhao; Congbo Huang; Shengzhi Li; Mengqiong Jia; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Plant Science, 2023)

Exploring the continuous cleavage-oxidation mechanism of the catalytic oxidation of cellulose to formic acid: A combined experimental and theoretical study - Gui-Hua Wei; Ting Lu; Hai-Yan Liu; Jiao-Xuan Bai; Qian Wang; Guang-Yue Li; Ying-Hua Liang (Fuel, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Experimental Study on Fractal Characteristics of Surface Roughness of Briquettes and their Effect on Wettability of Coal Samples - Min Yan; Hanxi Luo; Ting Yang; Dongjie Yan; Jianing Wei; Haifei Lin; Shugang Li (Natural Resources Research, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

Defensive Specialized Metabolites from the Latex of Euphorbia jolkinii - Shihong Luo; Chunshuai Huang; Juan Hua; Shuxi Jing; Linlin Teng; Ting Tang; Yan Liu; Shenghong Li (Journal of Chemical Ecology, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

The importance of moisture in regulating soil organic carbon content based on a comparison of “enzymic latch” and “iron gate” in Zoige Plateau peatland - Ruixuan Li; Hanqing Luo; Jianlan Yu; Ling Luo; Yan He; Shihuai Deng; Ouping Deng; Dezhi Shi; Jinsong He; Hong Xiao; Lilin Wang; Ting Lan (CATENA, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Calcium isotopic geochemistry of geothermal systems in the tectonically active southeastern Tibetan Plateau - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; Jun Zhong; Ting-Ting Ma; Jian Sun; Wen-Yan He; Cong-Qiang Liu (Science of The Total Environment, 2023)

The role of reactive astrocytes in neurotoxicity induced by ultrafine particulate matter - Ben Li; Xiaohan Chang; Xiaomin Liang; Ting Liu; Yongmei Shen; Qianwen Zhang; Xiaohui Yang; Yi Lyu; Liangpo Liu; Jianquan Guo; Meiqiong Wu; Yi Gao; et al. (Science of The Total Environment, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

Time-dependent effects of microplastics on soil bacteriome - Xuyuan Zhang; Yong Li; Junjie Lei; Ziqian Li; Qianlong Tan; Lingli Xie; Yunmu Xiao; Ting Liu; Xiaoyong Chen; Yafeng Wen; Wenhua Xiang; Yakov Kuzyakov; et al. (Journal of Hazardous Materials, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Association of urinary metal levels with metabolic syndrome in coal workers - Ben Li; Qianwen Zhang; Xiaohan Chang; Yongmei Shen; Ting Liu; Xiaomin Liang; Qian Gao; Liangpo Liu; Yulan Qiu; Xiaoyan Yan; Jianjun Huang; Tong Wang; et al. (Environmental Science and Pollution Research, 2023)

Comprehensive treatment strategy for diesel truck exhaust - Tian Li; Hai-Li Yang; Le-Tian Xu; Yu-Ting Zhou; Yong-Jun Min; Shi-Cheng Yan; Yong-Hui Zhang; Xiao-Ming Wang (Environmental Science and Pollution Research, 2023)

The application of a homemade boomer source in offshore seismic survey: From field data acquisition to post-processing - Jianglong Zheng; Linwei Li; Jinxing Xie; Ting Yan; Biao Jiang; Xiaoxin Huang; Gege Hui; Tianguang Li; Mingming Wen; Yifan Huang (Journal of Applied Geophysics, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Transcriptome analysis of the hepatopancreas in Penaeus vannamei under experimental infection with Enterocytozoon hepatopenaei (EHP) - Zheng Cao; Yang Gao; Jiahui Xu; Ning Yang; Ting Li; Linrui Chang; Lingjun Si; Dongchun Yan (Fish & Shellfish Immunology, 2023)

Anaerobic–anoxic–oxic biological treatment of high-strength, highly recalcitrant polyphenylene sulfide wastewater - Hui Guo; Hai-Yong Yao; Qi-Qi Huang; Ting Li; De-Yang Show; Ming Ling; Yue-Gen Yan; Kuan-Yeow Show; Duu-Jong Lee (Bioresource Technology, 2023)

DEGENERATED LEMMA (DEL) regulates lemma development and affects rice grain yield - You Jing; Chen Wenbo; He Zhifeng; Xiang Yan; Zhang XinFang; Wei Mi; Wu RuHui; Shen Wenqiang; Zhang Jun; Duan QianNan; He Guanghua; Li Yunfeng; et al. (Physiology and Molecular Biology of Plants, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Effects of H2O2 acclimation on the growth, polysaccharide production and tolerance performance of Nostoc flagelliforme - Shu-ting Liu; Shuai Wang; Na Han; Meng-yuan Li; Jian Li; Yan-ru Li; Shi-ru Jia; Pei-pei Han (Algal Research, 2023)

Coral reef resilience persisted for a millennium but has declined rapidly in recent decades - Ting Zhang; Tianran Chen; Sheng Liu; Xianzhi Lin; Shu Li; Wen Yan (Frontiers in Marine Science, 2023)
The lack of long-term records of coral community composition restricts our understanding of the contemporary ecological states of tropical reefs. Here we integrated paleo-ecological reconstruction, historical mortality evidence, and ecological survey data to determine the temporal variability in reef resilience of the Nansha atolls in the tropical western Pacific. Subfossil coral assemblages extracted from the reef cores exhibited no evidence of community shifts attributable to centennial-scale changes in El Niño variability during the last millennium, suggesting long-term stability in community structure and persistence of reef resilience. By contrast, ecological surveys revealed a major collapse in the reef ecosystem, and high-precision U-series dating of dead Acropora fragments indicated that this collapse occurred in recent decades and was especially relevant to several strong/extreme El Niño episodes. Frequent and intensive El Niño−Southern Oscillation and marine heatwaves have overwhelmed the reefs’ resistive and recovery capacity, thereby impairing reef resilience.

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

High-precision early warning system for rice cadmium accumulation risk assessment - Huili Yan; Hanyao Guo; Ting Li; Hezifan Zhang; Wenxiu Xu; Jianyin Xie; Xiaoyang Zhu; Yijun Yu; Jian Chen; Shouqing Zhao; Jun Xu; Minjun Hu; et al. (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Amorphous SnO2 decorated ZnSn(OH)6 promotes interfacial hydroxyl polarization for deep photocatalytic toluene mineralization - Lvcun Chen; Kanglu Li; Yan Yang; Ting Xue; Hong Wang; Ben Lei; Jianping Sheng; Fan Dong; Yanjuan Sun (Journal of Hazardous Materials, 2023)

Performance and mechanisms of biochar-assisted vermicomposting in accelerating di-(2-ethylhexyl) phthalate biodegradation in farmland soil - Zhen Zhen; Shuwen Luo; Yijie Chen; Gaoyang Li; Huijun Li; Ting Wei; Fengcheng Huang; Lei Ren; Yan-Qiu Liang; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2023)

The stability of cell structure and antioxidant enzymes are essential for fresh-cut potato browning - Tingting Wang; Ting Yan; Jingkun Shi; Yanmei Sun; Qingguo Wang; Qingqing Li (Food Research International, 2023)

Reducing the computational load – atomic multiconfiguration calculations based on configuration state function generators - Yan Ting Li; Kai Wang; Ran Si; Michel Godefroid; Gediminas Gaigalas; Chong Yang Chen; Per Jönsson (Computer Physics Communications, 2023)

GSH-responsive and O2-economizing virus-like nanocapsule for photothermal-augmented sonodynamic therapy - Jiajing Liu; Mengqi Li; Zhiyu Zhao; Xian Luo; Li Wang; Tingting Li; Cong Liu; Shengyu Wang; Ting Wu; Dong Yang; Yang Li; Peiyuan Wang; et al. (Chemical Engineering Journal, 2023)

Thermally insulating composite aerogel with both active absorption and passive insulation functions based on azobenzene-modified chitosan/oligomeric β-cyclodextrin - Chuan-Yan Huang; Jun-Feng Feng; Guo-Chen Li; Li-Guo Liao; Shu-Ting Fan; Jia-Xin Wang; Sheng Zhang; Bang-Jing Li (Chemical Engineering Journal, 2023)

Review on adsorbents in elemental mercury removal in coal combustion flue gas, smelting flue gas and natural gas - Ting Liu; Zhuo Xiong; Peng Ni; Zizhen Ma; Yan Tan; Zishun Li; Shengnan Deng; Yincui Li; Qirong Yang; Huawei Zhang (Chemical Engineering Journal, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

The toxic differentiation of micro- and nanoplastics verified by gene-edited fluorescent Caenorhabditis elegans - Wenxi Jiang; Wende Yan; Qianlong Tan; Yunmu Xiao; Yang Shi; Junjie Lei; Ziqian Li; Yuanyuan Hou; Ting Liu; Yong Li (Science of The Total Environment, 2023)

Eocene to Miocene Charophytes from the Qaidam Basin on the northern Tibetan Plateau and its calibration to the Geomagnetic Polarity Time Scale - Yi Xing; Bowen Song; Ting Li; Sha Li; Kui Yan; Qifei Wang; Haichun Zhang; Xiaoqiao Wan (Review of Palaeobotany and Palynology, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

GWAS-assisted genomic prediction of cadmium accumulation in maize kernel with machine learning and linear statistical methods - Huili Yan; Hanyao Guo; Wenxiu Xu; Changhua Dai; Wilson Kimani; Jianyin Xie; Hezifan Zhang; Ting Li; Feng Wang; Yijun Yu; Mi Ma; Zhuanfang Hao; et al. (Journal of Hazardous Materials, 2023)

A pectic polysaccharide from fresh okra (Abelmoschus esculentus L.) beneficially ameliorates CCl4-induced acute liver injury in mice by antioxidation, inhibition of inflammation and modulation of gut microbiota - Jing-Kun Yan; Chun Wang; Ting-Ting Chen; Jie Zhu; Xu Chen; Longqing Li; Xiaozhen Liu; Henan Zhang; Lin Li (Food and Chemical Toxicology, 2023)

Genome-wide identification of gap junction (connexins and pannexins) genes in black rockfish (Sebastes schlegelii): Evolution and immune response mechanism following challenge - Yiping Liu; Min Cao; Xu Yan; Xin Cai; Yuqing Li; Chao Li; Ting Xue (Fish & Shellfish Immunology, 2023)

Understanding the effect of environment on macrobenthic invertebrate in naturally occurring repeated mesohabitats from the warm-temperate zone river - Amit Jagannath Patil; Zhenhong Wang; Xiaole He; Pangen Li; Ting Yan; He Li (Ecohydrology & Hydrobiology, 2023)

Rational design of ZnO-based aqueous batteries for safe, fast, and reliable energy storage: Accomplishment of stable K+ storage/release - Ting Liu; Shuang Cheng; Luping Li; Xu Ji; Gyutae Nam; Xingbin Yan; Meilin Liu (Chemical Engineering Journal, 2023)

Design strategies of perovskite nanofibers electrocatalysts for water splitting: A mini review - Yaobin Wang; Yan Jiang; Yunxia Zhao; Xinlei Ge; Qian Lu; Ting Zhang; Dongsheng Xie; Meng Li; Yunfei Bu (Chemical Engineering Journal, 2023)

Volatile organic compound emissions from typical industries: Implications for the importance of oxygenated volatile organic compounds - Wenjing Wang; Yunzhi Yan; Hua Fang; Jun Li; Shuping Zha; Ting Wu (Atmospheric Pollution Research, 2023)

Identification of major quantitative trait loci and candidate genes for seed weight in soybean - Mengge Xu; Keke Kong; Long Miao; Jianbo He; Tengfei Liu; Kai Zhang; Xiuli Yue; Ting Jin; Junyi Gai; Yan Li (Theoretical and Applied Genetics, 2023)
Key message Four major quantitative trait loci for 100-seed weight were identified in a soybean RIL population under five environments, and the most likely candidate genes underlying these loci were identified. Abstract Seed weight is an important target of soybean breeding. However, the genes underlying the major quantitative trait loci (QTL) controlling seed weight remain largely unknown. In this study, a soybean population of 300 recombinant inbred lines (RILs) derived from a cross between PI595843 (PI) and WH was used to map the QTL and identify candidate genes for seed weight. The RIL population was genotyped through whole genome resequencing, and phenotyped for 100-seed weight under five environments. A total of 38 QTL were detected, and four major QTL, each explained at least 10% of the variation in 100-seed weight, were identified. Six candidate genes within these four major QTL regions were identified by analyses of their tissue expression patterns, gene annotations, and differential gene expression levels in soybean seeds during four developmental stages between two parental lines. Further sequence variation analyses revealed a C to T substitution in the first exon of the Glyma.19G143300 , resulting in an amino acid change between PI and WH, and thus leading to a different predicted kinase domain, which might affect its protein function. Glyma.19G143300 is highly expressed in soybean seeds and encodes a leucine-rich repeat receptor-like protein kinase (LRR-RLK). Its predicted protein has typical domains of LRR-RLK family, and phylogenetic analyses reveled its similarity with the known LRR-RLK protein XIAO ( LOC_Os04g48760 ), which is involved in controlling seed size. The major QTL and candidate genes identified in this study provide useful information for molecular breeding of new soybean cultivars with desirable seed weight.

Rice glycosyltransferase gene UGT2 functions in salt stress tolerance under the regulation of bZIP23 transcription factor - Ting Wang; Xing-kun Li; Xi Liu; Xian-qin Yang; Yan-jie Li; Bing-kai Hou (Plant Cell Reports, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

The taxonomic revision of Melanogaster (Paxillaceae, Boletales) in China based on molecular and morphological evidence - Yu-yan Xu; Xiang-yuan Yan; Ting Li; Tao-yu Zhao; Jing-chong Lv; Li Fan (Mycological Progress, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Summary of research progress on separation and extraction of valuable metals from Bayer red mud - Kun Wang; Zhihe Dou; Yan Liu; Xiaofei Li; Guozhi Lv; Ting-an Zhang (Environmental Science and Pollution Research, 2022)

Facile one-step synthesis of PhC2Cu nanowires with enhanced photocatalytic performance - Gao-yu Zhao; Hai-yan Li; Yu Yang; Qing-hua Zhao; Ting-ting Su; Jiang-li Ma (Environmental Science and Pollution Research, 2022)

ZmSPO11-2 is critical for meiotic recombination in maize - Menghan Li; Shuyue Li; Yan He; Yan Wang; Ting Zhang; Ping Li; Yan He (Chromosome Research, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

AKR1B10 accelerates the production of proinflammatory cytokines via the NF-κB signaling pathway in colon cancer - Cong Liu; Lei Shi; Wanyun Li; Zilan Huang; Shengyu Wang; Peilan Xu; Tingting Li; Zhenyu Li; Fanghong Luo; Wengang Li; Jianghua Yan; Ting Wu (Journal of Molecular Histology, 2022)

Antifungal and Antibiofilm In Vitro Activities of Ursolic Acid on Cryptococcus neoformans - Wen-Jing Wang; Chan-Chan Liu; Yan-Tong Li; Miao-Qian Li; Yu-Ting Fu; Xin-Chen Li; Jie-Kang; Wei-Dong Qian (Current Microbiology, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Two novel and efficient plant composites for the degradation of oxytetracycline: nanoscale ferrous sulphide supported on rape straw waste - Yan Yang; Xiaoxun Xu; Shirong Zhang; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Junren Xian; Ting Li; Yulin Pu; Wei Zhou; Gang Xiang (Environmental Science and Pollution Research, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Human Umbilical Cord-Derived Mesenchymal Stem Cells Ameliorate Skin Aging of Nude Mice Through Autophagy-Mediated Anti-Senescent Mechanism - Ting Li; Li Zhou; Mengqiang Fan; Zuxiang Chen; Li Yan; Haishan Lu; Ming Jia; Huiling Wu; Letian Shan (Stem Cell Reviews and Reports, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Influence of nitrogen wet deposition on nitrogen output in a typical watershed in the Three Gorges Reservoir Area - Chen-dong Lu; Liu-yi Zhang; Kun Yan; Yu-kuan Wang; Shan-gao Xiong; Chen-tao Huang; Ting-zhen Li; Mao-fei Ni (Journal of Mountain Science, 2022)

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Prenylated coumarins from the fruits of Artocarpus heterophyllus with their potential anti-inflammatory and anti-HIV activities - Lei Tao; Ya-Ting Zhuo; Ze-Hua Qiao; Juan Li; Hao-Xuan Tang; Qiao-Mei Yu; Yun-Yao Liu; Yan-Ping Liu (Natural Product Research, 2022)

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Reproductive Dynamics of the Large Yellow Croaker Larimichthys crocea (Sciaenidae), A Commercially Important Fishery Species in China - Li-ting Yan; Yan Jiang; Qing Xu; Guang-mao Ding; Xin-yi Chen; Min Liu (Frontiers in Marine Science, 2022)
The large yellow croaker Larimichthys crocea (Richardson, 1846) (Sciaenidae) is distributed in southern Yellow Sea, East China Sea, and northern South China Sea of China and is a commercially important nearshore fishery species. L. crocea was listed on the IUCN Red List as “Critically Endangered” in 2020 mainly due to the over-exploration of its spawning and over-wintering aggregations in the 1950s–1980s throughout its distribution region. However, detailed studies on reproductive dynamics of L. crocea were limited in the past three decades. In this study, the reproductive dynamics of L. crocea was examined in the traditional Guanjingyang (GJY) spawning ground, one of the 15 well-known ones in its distribution region. Samples were collected using set nets from April 2019 to November 2021 to ensure at least 20 samples for all 12 months. A total of 1,006 individuals were caught, ranging from 46 to 391 mm standard length (SL) and 1.45 to 1,110.05 g body weight (BW). A growth dimorphism was found between sexes with females heavier than males when body sizes exceeded 61 mm SL (non-parametric ANCOVA, p < 0.01). Gonad histology of all 1,006 individuals revealed, for the first time, that L. crocea was able to spawn almost year-round for both females and males. Two spawning peaks, spring and autumn, were identified in March and May and in November for females and in April to June and in October to November for males. The minimum sizes at sexual maturity were 160 mm SL for females and 112 mm SL for male. The sizes at 50% sexual maturity were 187.2 mm SL for females and 150.2 mm SL for males. Results showed that the minimum SL for female maturity decreased about 20% in the past six decades. The spawning peaks were 2 months earlier in spring and 1 month extension in autumn in GJY. Clearly, the national fishing moratorium regulation in May to August, an important fishery management measure in China, can only protect the spring spawning peak partly. Further evaluation on the influence of climate change on reproductive strategies and stock recruitment of L. crocea is highly recommended.

Modular-level alterations of single-subject gray matter networks in schizophrenia - Yuxiang Guo; Yunxiao Ma; GongShu Wang; Ting Li; Tong Wang; Dandan Li; Jie Xiang; Tianyi Yan; Bin Wang; Miaomiao Liu (Brain Imaging and Behavior, 2022)

Baicalin attenuates amyloid β oligomers induced memory deficits and mitochondria fragmentation through regulation of PDE-PKA-Drp1 signalling - Hai-Yang Yu; Ye Zhu; Xin-Li Zhang; Lei Wang; Yan-Meng Zhou; Fang-Fang Zhang; Han-Ting Zhang; Xiao-Min Zhao (Psychopharmacology, 2022)

Optimizing Fertilizer Management Based on Controlled-Release Fertilizer to Improve Yield, Quality, and Reduce Fertilizer Application on Apples - Junyin Li; Yan Liu; Yafu Tang; Junfei Shao; Ting Xu; Ronghui Ma; Yuanmao Jiang; Dongdong Cheng (Journal of Soil Science and Plant Nutrition, 2022)

Myrothecol A, a new alkylresorcinol with cytotoxicity from Myrothecium sp. - Zhen-Hua Li; Hui-Yuan Yang; Wen-Ting Zhu; Dong-Dong Jing; Shi-Neng Li; Peng-Ke Yan (Natural Product Research, 2022)

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Efficiency and comprehensive risk assessment of soil Pb and Cd by washing technique with three biodegradable eluents - Qinmei Zhong; Shirong Zhang; Xiaomei Pan; Guiyin Wang; Xiaoxun Xu; Ting Li; Wei Zhou; Yan He; Ling Luo; Yan Liu; Lulu Long (Environmental Science and Pollution Research, 2021)

Reduced acetylcholine and elevated muscarinic receptor 2 in duodenal mucosa contribute to the impairment of mucus secretion in 6-hydroxydopamine-induced Parkinson’s disease rats - Jing-Ting Yan; Xiao-Yu Liu; Jing-Hua Liu; Guang-Wen Li; Li-Fei Zheng; Xiao-Li Zhang; Yue Zhang; Xiao-Yan Feng; Jin-Xia Zhu (Cell and Tissue Research, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Hygrophorus russula complex (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Moreno Gabriel; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2021)

Quantitative microbial risk assessment for occupational health of temporary entrants and staffs equipped with various grade PPE and exposed to microbial bioaerosols in two WWTPs - Cheng Yan; Ya-li Leng; Jun-ting Wu (International Archives of Occupational and Environmental Health, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Analysis of variation patterns in rice milled quality in the offspring of indica–japonica hybridization - Ting Mao; Zhan Zhang; Shan-Jun Ni; Yi-Zhou Zhao; Xin Li; Li-Li Zhang; Yan Liu; Xu Li (Genetic Resources and Crop Evolution, 2021)

Enhanced removal of Cd (II) from aqueous solution by EDTA functionalized three-dimensional magnetic nitrogen-doped porous carbon - Ting Zhang; Changyu Li; Weijie Shi; Yifan Zhu; Yan Chen; Yongxin Nie; Jianchao Sun; Shiyun Ai (Environmental Science and Pollution Research, 2021)

Erratum to: Spatio-temporal variation of Fraction of Photosynthetically Active Radiation absorbed by vegetation in the Hengduan Mountains, China - Zheng-lan Yang; Ting-bin Zhang; Gui-hua Yi; Jing-ji Li; Yan-bin Qin; Yang Chen (Journal of Mountain Science, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

The hand-arm vibration syndrome associated with the grinding of handheld workpieces in a subtropical environment - Nuoyan Wei; Hansheng Lin; Ting Chen; Bin Xiao; Maosheng Yan; Li Lang; Hongyu Yang; Shan Wu; Paul-Émile Boileau; Qingsong Chen (International Archives of Occupational and Environmental Health, 2021)

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Abnormalities in hemispheric lateralization of intra- and inter-hemispheric white matter connections in schizophrenia - Dandan Li; Wenjing Tang; Ting Yan; Nan Zhang; Jie Xiang; Yan Niu; Bin Wang (Brain Imaging and Behavior, 2021)

APOE ε4 and cognitive reserve effects on the functional network in the Alzheimer’s disease spectrum - Ting Li; Bin Wang; Yuan Gao; Xin Wang; Ting Yan; Jie Xiang; Yan Niu; Tiantian Liu; Duanduan Chen; Boyan Fang; Yunyan Xie; Shintaro Funahashi; et al. (Brain Imaging and Behavior, 2021)

Spatio-temporal variation of Fraction of Photosynthetically Active Radiation absorbed by vegetation in the Hengduan Mountains, China - Zheng-Ian Yang; Ting-bin Zhang; Gui-hua Yi; Jing-ji Li; Yan-bin Qin; Yang Chen (Journal of Mountain Science, 2021)

CYT387, a Novel JAK2 Inhibitor, Suppresses IL-13-Induced Epidermal Barrier Dysfunction Via miR-143 Targeting IL-13Rα1 and STAT3 - Yan Zu; Xiao-Fei Chen; Qiang Li; Shu-Ting Zhang (Biochemical Genetics, 2021)

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

The Combined Effects of Increased pCO2 and Warming on a Coastal Phytoplankton Assemblage: From Species Composition to Sinking Rate - Yuanyuan Feng; Fei Chai; Mark L. Wells; Yan Liao; Pengfei Li; Ting Cai; Ting Zhao; Feixue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
In addition to ocean acidification, a significant recent warming trend in Chinese coastal waters has received much attention. However, studies of the combined effects of warming and acidification on natural coastal phytoplankton assemblages here are scarce. We conducted a continuous incubation experiment with a natural spring phytoplankton assemblage collected from the Bohai Sea near Tianjin. Experimental treatments used a full factorial combination of temperature (7 and 11°C) and pCO 2 (400 and 800 ppm) treatments. Results suggest that changes in pCO 2 and temperature had both individual and interactive effects on phytoplankton species composition and elemental stoichiometry. Warming mainly favored the accumulation of picoplankton and dinoflagellate biomass. Increased pCO 2 significantly increased particulate organic carbon to particulate organic phosphorus (C:P) and particulate organic carbon to biogenic silica (C:BSi) ratios, and decreased total diatom abundance; in the meanwhile, higher pCO 2 significantly increased the ratio of centric to pennate diatom abundance. Warming and increased pCO 2 both greatly decreased the proportion of diatoms to dinoflagellates. The highest chlorophyll a biomass was observed in the high pCO 2 , high temperature phytoplankton assemblage, which also had the slowest sinking rate of all treatments. Overall, there were significant interactive effects of increased pCO 2 and warming on dinoflagellate abundance, pennate diatom abundance, diatom vs. dinoflagellates ratio and the centric vs. pennate ratio. These findings suggest that future ocean acidification and warming trends may individually and cumulatively affect coastal biogeochemistry and carbon fluxes through shifts in phytoplankton species composition and sinking rates.

Aryl hydrocarbon receptor promotes lipid droplet biogenesis and metabolic shift in respiratory Club cells - Hsueh-Chun Wang; Kwei-Yan Liu; Li-Ting Wang; Shih-Hsien Hsu; Shao-Chun Wang; Shau-Ku Huang (Human Cell, 2021)

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Warming leads to more closed nitrogen cycling in nitrogen‐rich tropical forests - Zhiyang Lie; Wenjuan Huang; Xujun Liu; Guoyi Zhou; Junhua Yan; Yuelin Li; Chumin Huang; Ting Wu; Xiong Fang; Mengdi Zhao; Shizhong Liu; Guowei Chu; et al. (Global Change Biology, 2021)
Warming may have profound effects on nitrogen (N) cycling by changing plant N demand and underground N supply. However, large uncertainty exists regarding how warming affects the integrated N dynamic in tropical forests. We translocated model plant‐soil ecosystems from a high‐altitude site (600 m) to low‐altitude sites at 300 and 30 m to simulate warming by 1.0°C and 2.1°C, respectively, in tropical China. The effects of experimental warming on N components in plant, soil, leaching, and gas were studied over 6 years. Our results showed that foliar δ 15 N values and inorganic N (NH 4 ‐N and NO 3 ‐N) leaching were decreased under warming, with greater decreases under 2.1°C of warming than under 1.0°C of warming. The 2.1°C of warming enhanced plant growth, plant N uptake, N resorption, and fine root biomass, suggesting higher plant N demand. Soil total N concentrations, NO 3 ‐N concentrations, microbial biomass N and arbuscular mycorrhizal fungal abundance were decreased under 2.1°C of warming, which probably restricted bioavailable N supply and arbuscular mycorrhizal contribution of N supply to plants. These changes in plants, soils and leaching indicated more closed N cycling under warming, the magnitude of which varied over time. The closed N cycling became pronounced during the first 3 years of warming where the sustained reductions in soil inorganic N could not meet plant N demand. Subsequently, the closed N cycling gradually mitigated, as observed by attenuated positive responses of plant growth and less negative responses of microbial biomass N to warming during the last 3 years. Overall, the more closed N cycling under warming could facilitate ecosystem N retention and affect production in these tropical forests, but these effects would be eventually mitigated with long‐term warming probably due to the restricted plant growth and microbial acclimation.

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

OsRbohB-mediated ROS production plays a crucial role in drought stress tolerance of rice - Yi Shi; Yan-Li Chang; Hai-Tao Wu; Abdullah Shalmani; Wen-Ting Liu; Wen-Qiang Li; Jian-Wei Xu; Kun-Ming Chen (Plant Cell Reports, 2020)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Dynamic reconfiguration of functional brain networks supporting response inhibition in a stop-signal task - Bin Wang; Yaqing Hao; Qionghui Zhan; Shuo Zhao; Dandan Li; Sumaira Imtiaz; Jie Xiang; Jinglong Wu; Hidenao Fukuyama; Ting Yan (Brain Imaging and Behavior, 2020)

Multiple Xanthomonas campestris pv. campestris 8004 type III effectors inhibit immunity induced by flg22 - Yan Huang; Tongqi Li; Ting Xu; Zizhong Tang; Jingya Guo; Yi Cai (Planta, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

A photogrammetric method for laboratory-scale investigation on 3D landslide dam topography - Hao Wu; De-feng Zheng; Yan-jun Zhang; Dong-yang Li; Ting-kai Nian (Bulletin of Engineering Geology and the Environment, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Puerarin Alleviates Lipopolysaccharide-Induced Myocardial Fibrosis by Inhibiting PARP-1 to Prevent HMGB1-Mediated TLR4-NF-κB Signaling Pathway - Shu-Yuan Ni; Xing-Long Zhong; Ze-Hua Li; Dong-Jian Huang; Wen-Ting Xu; Yan Zhou; Cai-Wen Ou; Min-Sheng Chen (Cardiovascular Toxicology, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

The relation of structure and metal-support interaction with three-way catalytic performance of Rh/(Ce,Zr,La)O2 catalysts - Ting Wang; Yan Li; Ren-xian Zhou (Environmental Science and Pollution Research, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

A new triterpenoid glucoside from Leucas zeylanica - Guang-Ying Chen; Bin Zhang; Ting Zhao; Najat Nidhal; Wang Jia-Li; Xue-Ming Zhou; Dai Chun-Yan (Natural Product Research, 2020)

Ocean surface current retrieval at Hangzhou Bay from Himawari-8 sequential satellite images - Zhenye Zhu; Xupu Geng; Shihui Li; Ting Xie; Xiao-Hai Yan (Science China Earth Sciences, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Coix seed oil prolongs lifespan and enhances stress resistance in Caenorhabditis elegans - Xin-Yan Chen; De-Chun Liao; Ying-Ting Yu; Cong-Min Wei; Ling-Yan Xuan; Shan Li; Hong-Bing Wang (Biogerontology, 2020)

Effect of Mechanical Damage on the Thermal Conductivity of Granite - Zheng-Wei Li; Xia-Ting Feng; Yan-Jun Zhang; Yan-Hua Gong; Guo-Qiang Zhu (Rock Mechanics and Rock Engineering, 2020)

The Arabidopsis UDP-glycosyltransferase75B1, conjugates abscisic acid and affects plant response to abiotic stresses - Ting-Ting Chen; Fang-Fei Liu; Dong-Wang Xiao; Xiao-Yi Jiang; Pan Li; Shu-Man Zhao; Bing-kai Hou; Yan-jie Li (Plant Molecular Biology, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Impacts of climate change, population growth, and urbanization on future population exposure to long-term temperature change during the warm season in China - Wei Zhang; Ying Li; Zhuang Li; Xin Wei; Ting Ren; Jie Liu; Yan Zhu (Environmental Science and Pollution Research, 2020)

Neurocognitive impairment in Asian childhood cancer survivors: a systematic review - Liwen Peng; Perri Pui-Yan Yam; Lok Sum Yang; Satomi Sato; Chi Kong Li; Yin Ting Cheung (Cancer and Metastasis Reviews, 2020)

Fungal endophytic communities of two wild Rosa varieties and the role of an endophytic Seimatosporium sp. in enhancing host plant powdery mildew resistance - Yi Zhao; Xiu-ling Ji; Ting Shen; Wen-ting Tang; Shao-shi Li; Zheng-qing Zhu; Jitendra Kumar; Hai-yan Li (Plant and Soil, 2020)

Adjuvant therapy with Astragalus membranaceus for post-stroke fatigue: a systematic review - Li Xu; Xiao-Yan Xu; Xue-Qin Hou; Fu-Gang Wang; Shan Gao; Han-Ting Zhang (Metabolic Brain Disease, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Metabolomics and physiological analyses reveal β-sitosterol as an important plant growth regulator inducing tolerance to water stress in white clover - Zhou Li; Bizhen Cheng; Bin Yong; Ting Liu; Yan Peng; Xinquan Zhang; Xiao Ma; Linkai Huang; Wei Liu; Gang Nie (Planta, 2019)

The Rho kinase inhibitor fasudil attenuates Aβ1–42-induced apoptosis via the ASK1/JNK signal pathway in primary cultures of hippocampal neurons - Ye Gao; Yuqing Yan; Qingli Fang; Nianping Zhang; Gajendra Kumar; Jihong Zhang; Li-Juan Song; Jiezhong Yu; Linhu Zhao; Han-Ting Zhang; Cun-Gen Ma (Metabolic Brain Disease, 2019)

Indoor formaldehyde removal by three species of Chlorphytum Comosum under the long-term dynamic fumigation system - Jian Li; Jiaochan Zhong; Ting Zhan; Qinghui Liu; Liushui Yan; Mingming Lu (Environmental Science and Pollution Research, 2019)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Correction to: Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

MicroRNA-494 targets PTEN and suppresses PI3K/AKT pathway to alleviate hypertrophic scar formation - Ting He; Yue Zhang; Yang Liu; Hongtao Wang; Wanfu Zhang; Jiaqi Liu; Na Li; Yan Li; Luxu Wang; Songtao Xie; Dahai Hu (Journal of Molecular Histology, 2019)

Crystal Transformation of β-CD-MOF Facilitates Loading of Dimercaptosuccinic Acid - Yuehuai Xiong; Li Wu; Tao Guo; Caifen Wang; Wenting Wu; Yan Tang; Ting Xiong; Yong Zhou; Weifeng Zhu; Jiwen Zhang (AAPS PharmSciTech, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

The 3D-Printing Technology of Geological Models Using Rock-Like Materials - Xia-Ting Feng; Yan-Hua Gong; Yang-Yi Zhou; Zheng-Wei Li; Xu-Feng Liu (Rock Mechanics and Rock Engineering, 2019)

Comparison of volatile profiles and bioactive components of sun-dried Pu-erh tea leaves from ancient tea plants on Bulang Mountain measured by GC-MS and HPLC - Wen-jie Zhang; Cong Liu; Rui-juan Yang; Ting-ting Zheng; Miao-miao Zhao; Li Ma; Liang Yan (Journal of Zhejiang University-SCIENCE B, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

Reduced hemispheric asymmetry of brain anatomical networks in attention deficit hyperactivity disorder - Dandan Li; Ting Li; Yan Niu; Jie Xiang; Rui Cao; Bo Liu; Hui Zhang; Bin Wang (Brain Imaging and Behavior, 2019)

Fine mapping of a novel yellow-green leaf 14 (ygl14) mutant in rice - Jia Tan; Ting Zhang; Saisai Xia; Meng Yan; Fengfei Li; Xianchun Sang; Guanghua He; Yinghua Ling (Euphytica, 2019)

OsSGT1 Is a Glucosyltransferase Gene Involved in the Glucose Conjugation of Phenolics in Rice - Qian Liu; Yu-ying Zhang; Lu Chen; Ting-ting Chen; Yan-jie Li; Bing-kai Hou (Plant Molecular Biology Reporter, 2019)

Four new species of Hydnobolites (sequestrate Pezizaceae, Ascomycota) from China - Ting Li; Meng Chen; Yu-Yan Xu; Li Fan (Mycological Progress, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Acid pretreatment improves microtuberization of potato plantlets - Yue Teng; Yan Zhang; Jin Ting Guo; Yu Liang Gao; Kui Hua Li (In Vitro Cellular & Developmental Biology - Plant, 2019)

Drought differently affects growth properties, leaf ultrastructure, nitrogen absorption and metabolism of two dominant species of Hippophae in Tibet Plateau - Juan Chen; Yudong Li; Yan Luo; Weiguo Tu; Ting Wan (Acta Physiologiae Plantarum, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Characterization of the complete chloroplast genome of a critically endangered decaploid rose species, Rosa praelucens (Rosaceae) - Hong-ying Jian; Shu-dong Zhang; Ting Zhang; Xian-qin Qiu; Hui-jun Yan; Shu-bin Li; Qi-gang Wang; Kai-xue Tang (Conservation Genetics Resources, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Sex Differences in Neuropathology and Cognitive Behavior in APP/PS1/tau Triple-Transgenic Mouse Model of Alzheimer’s Disease - Jun-Ting Yang; Zhao-Jun Wang; Hong-Yan Cai; Li Yuan; Meng-Ming Hu; Mei-Na Wu; Jin-Shun Qi (Neuroscience Bulletin, 2018)

DNA analysis reveals rich diversity of Hydnotrya with emphasis on the species found in China - Yu-Yan Xu; Yan-Wei Wang; Ting Li; Xiang-Yuan Yan; Li Fan (Mycological Progress, 2018)

Neuroinflammation and Neuroimmunomodulation in Alzheimer’s Disease - Yin Hong; Jun Xu; Yue Hu; Lin Li; Zhen Dong; Ting-ke Zhu; Yan-qiu Wei (Current Pharmacology Reports, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Cross-cultural adaption and psychometric properties of the Chinese version of the Diabetes Behavior Rating Scale: a pilot study - Jing Zhu; Jingjing Xu; Yang Chen; Yong Gu; Li Ji; Yufeng Zhou; Min Zhu; Hsiang-Ting Hsu; Xiaoping Huang; Cuiping Yuan; Yun Shi; Dan Yan; et al. (Science China Life Sciences, 2018)

Exclosure on CT-measured soil macropore characteristics in the Inner Mongolia grassland of northern China - Xia Hu; Yan-Li Lyu; Yong Liu; Xiao-Yan Li; Zhen-Ting Sun; Zong-Chao Li; Ya-Qian Cheng; Lan-Lan Guo; Lian-You Liu (Journal of Soils and Sediments, 2018)

Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Simulating and mapping the spatial and seasonal effects of future climate and land -use changes on ecosystem services in the Yanhe watershed, China - Dengshuai Chen; Jing Li; Zixiang Zhou; Yan Liu; Ting Li; Jingya Liu (Environmental Science and Pollution Research, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Deletion of TpKu70 facilitates gene targeting in Talaromyces pinophilus and identification of TpAmyR involvement in amylase production - Ting Zhang; Shuai Zhao; Lu-Sheng Liao; Cheng-Xi Li; Gui-Yan Liao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2017)

Protective effect of dihydropteridine reductase against oxidative stress is abolished with A278C mutation - Yan-ting Gu; Yan-chun Wang; Hao-jun Zhang; Ting-ting Zhao; Si-fan Sun; Hua Wang; Bin Zhu; Ping Li (Journal of Zhejiang University-SCIENCE B, 2017)

A system to identify inhibitors of mTOR signaling using high-resolution growth analysis in Saccharomyces cerevisiae - Mitchell B. Lee; Daniel T. Carr; Michael G. Kiflezghi; Yan Ting Zhao; Deborah B. Kim; Socheata Thon; Margarete D. Moore; Mary Ann K. Li; Matt Kaeberlein (GeroScience, 2017)

Identification and functional characterization of DzS3GT, a cytoplasmic glycosyltransferase catalyzing biosynthesis of diosgenin 3-O-glucoside in Dioscorea zingiberensis - Ting Ye; Wei Song; Jia-Jiao Zhang; Mei An; Shan Feng; Shan Yan; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

DNA hypermethylation of sFRP5 contributes to indoxyl sulfate-induced renal fibrosis - Yanlin Yu; Xu Guan; Ling Nie; Yong Liu; Ting He; Jiachuan Xiong; Xinli Xu; Yan Li; Ke Yang; Yiqin Wang; Yunjian Huang; Bing Feng; et al. (Journal of Molecular Medicine, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Verticillium dahliae manipulates plant immunity by glycoside hydrolase 12 proteins in conjunction with carbohydrate‐binding module 1 - Yue‐Jing Gui; Jie‐Yin Chen; Dan‐Dan Zhang; Nan‐Yang Li; Ting‐Gang Li; Wen‐Qi Zhang; Xin‐Yan Wang; Dylan P. G. Short; Lei Li; Wei Guo; Zhi‐Qiang Kong; Yu‐Ming Bao; et al. (Environmental Microbiology, 2017)
Summary Glycoside hydrolase 12 (GH12) proteins act as virulence factors and pathogen‐associated molecular patterns (PAMPs) in oomycetes. However, the pathogenic mechanisms of fungal GH12 proteins have not been characterized. In this study, we demonstrated that two of the six GH12 proteins produced by the fungus Verticillium dahliae Vd991, VdEG1 and VdEG3 acted as PAMPs to trigger cell death and PAMP‐triggered immunity (PTI) independent of their enzymatic activity in Nicotiana benthamiana . A 63‐amino‐acid peptide of VdEG3 was sufficient for cell death‐inducing activity, but this was not the case for the corresponding peptide of VdEG1. Further study indicated that VdEG1 and VdEG3 trigger PTI in different ways: BAK1 is required for VdEG1‐ and VdEG3‐triggered immunity, while SOBIR1 is specifically required for VdEG1‐triggered immunity in N. benthamiana . Unlike oomycetes, which employ RXLR effectors to suppress host immunity, a carbohydrate‐binding module family 1 (CBM1) protein domain suppressed GH12 protein‐induced cell death. Furthermore, during infection of N. benthamiana and cotton, VdEG1 and VdEG3 acted as PAMPs and virulence factors, respectively indicative of host‐dependent molecular functions. These results suggest that VdEG1 and VdEG3 associate differently with BAK1 and SOBIR1 receptor‐like kinases to trigger immunity in N. benthamiana , and together with CBM1‐containing proteins manipulate plant immunity.

Sap flow-based transpiration in Phyllostachys pubescens: applicability of the TDP methodology, age effect and rhizome role - Zhao Xiu-hua; Zhao Ping; Zhang Zhen-zhen; Zhu Li-wei; Niu Jun-feng; Ni Guang-yan; Hu Yan-ting; Ouyang Lei (Trees, 2017)

Serum Resistin Levels May Contribute to an Increased Risk of Acute Cerebral Infarction - Xiao-Liu Dong; Shi-Jun Xu; Li Zhang; Xiu-Qing Zhang; Ting Liu; Qiu-Yan Gao; Qing-Qiang Qian; Bao-Liang Sun; Ming-Feng Yang (Molecular Neurobiology, 2017)

Antidepressant-Like and Anxiolytic-Like Effects of ZBD-2, a Novel Ligand for the Translocator Protein (18 kDa) - Dong-sheng Wang; Jing Han; Shuo Li; Ting Sun; Yan-yan Guo; Wen-bo Kang; Zhen Tian; Jian-ning Zhao; Gang Liu; Shui-bing Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2017)

Molecular phylogeography and paleodistribution modeling of the boreal tree species Ulmus lamellosa (T.Wang et S. L. Chang) (Ulmaceae) in China - Li Liu; Wei Chen; Dong-Ting Yan; Jing Li; Lin Liu; Yi-Ling Wang (Tree Genetics & Genomes, 2017)

Vimentin is important in the neural differentiation of PC12 cells promoted by sialylation - Li Hui Wu; Xiao Ting Shao; Jun Xia Guo; Hui Sun; Qi Chen; Jing Pan; Qian Qian Cai; Yi Wei Dong; Zhong Yi Chen; Xiao Mei Yan; Min Peng; Nanbert Zhong; et al. (Glycoconjugate Journal, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Influence of genetic polymorphisms in cytochrome P450 oxidoreductase on the variability in stable warfarin maintenance dose in Han Chinese - Wu-Tao Zeng; Qing Xu; Cheng-Hsun Li; Wei-Yan Chen; Xiu-Ting Sun; Xiang Wang; Yi-Ying Yang; Hui Shi; Zhi-Sheng Yang (European Journal of Clinical Pharmacology, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Investigation of diarrhetic shellfish toxins in Lingshan Bay, Yellow Sea, China, using solid-phase adsorption toxin tracking (SPATT) - Feng-Ling Li; Zhao-Xin Li; Meng-Meng Guo; Hai-Yan Wu; Ting-Ting Zhang; Cai-Hu Song (Food Additives & Contaminants: Part A, 2016)

Predicting potential antitumor targets of Aconitum alkaloids by molecular docking and protein–ligand interaction fingerprint - Jing-wei Liang; Ting-jian Zhang; Zuo-jing Li; Zai-xing Chen; Xin-li Yan; Fan-hao Meng (Medicinal Chemistry Research, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Silibinin Prevents Autophagic Cell Death upon Oxidative Stress in Cortical Neurons and Cerebral Ischemia-Reperfusion Injury - Min Wang; Yu-Jiao Li; Yi Ding; Hui-Nan Zhang; Ting Sun; Kun Zhang; Le Yang; Yan-Yan Guo; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2016)

Phytosterol content and the campesterol:sitosterol ratio influence cotton fiber development: role of phytosterols in cell elongation - Shasha Deng; Ting Wei; Kunling Tan; Mingyu Hu; Fang Li; Yunlan Zhai; Shue Ye; Yuehua Xiao; Lei Hou; Yan Pei; Ming Luo (Science China Life Sciences, 2016)

Identification and Functional Analysis of the NADK Gene Family in Wheat - Xiang Wang; Wen-Yan Li; Mao-Mao Zhang; Yin-Tao Gao; Wen-Ting Liu; Wen-Qiang Li; Izhar Muhammad; Kun-Ming Chen (Plant Molecular Biology Reporter, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Impact of bacteria in nasal aspirates on disease severity of bronchiolitis - Wujun Jiang; Ting Wang; Li Li; Wei Ji; Yuqing Wang; Yongdong Yan (Infectious Diseases, 2016)

Morphological study of Ophidascaris excavata Hsü & Hoeppli, 1931 (Ascaridida: Ascarididae) from Gloydius brevicaudus (Stejneger) (Reptilia: Viperidae) - Liang Li; Wen-Ting Zhao; Hui-Xia Chen; Yan-Ning Guo; Lu-Ping Zhang (Systematic Parasitology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Ultrastructure of Ascaridia galli (Schrank, 1788) (Nematoda: Ascaridida) from the endangered green peafowl Pavo muticus Linnaeus (Galliformes: Phasianidae) - Ting Zhao; Yan-Ning Guo; Lu-Ping Zhang; Liang Li (Acta Parasitologica, 2016)
Ascaridia galli (Schrank, 1788) is a common parasite of various galliform birds worldwide. Although A. galli has been extensively studied by many author, knowledge of the morphology of this species in detail is still insufficient. In the present paper, the detailed morphology of A. galli was further studied using light and scanning electron microscopy, based on specimens collected from the endangered green peafowl Pavo muticus Linnaeus (Galliformes: Phasianidae) in China. The results revealed some erroneous and previously unreported morphological features, including the lips lacking real denticles, the lateral alae beginning at some distance posterior to the base of the ventrolateral lips and the caudal papillae with 4 different morphotypes. The present morphological and morphometric data complement previous descriptions and enable us to recognize this species more precisely.

NK cell-based cancer immunotherapy: from basic biology to clinical application - Yang Li; Jie Yin; Ting Li; Shan Huang; Han Yan; JianMei Leavenworth; Xi Wang (Science China Life Sciences, 2015)

Effective conversion of maize straw wastes into bio-hydrogen by two-stage process integrating H2 fermentation and MECs - Yan-Hong Li; Yan-Xia Bai; Chun-Mei Pan; Wei-Wei Li; Hui-Qin Zheng; Jing-Nan Zhang; Yao-Ting Fan; Hong-Wei Hou (Environmental Science and Pollution Research, 2015)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

Noninvasive Characterization of Vascular Tone by Model-Based System Identification in Healthy and Heart Failure Patients - Ya-Li Zheng; Bryan P. Yan; Yuan-Ting Zhang; Carmen C. Y. Poon (Annals of Biomedical Engineering, 2015)

Effects of cold acclimation on sugar metabolism and sugar-related gene expression in tea plant during the winter season - Chuan Yue; Hong-Li Cao; Lu Wang; Yan-Hua Zhou; Yu-Ting Huang; Xin-Yuan Hao; Yu-Chun Wang; Bo Wang; Ya-Jun Yang; Xin-Chao Wang (Plant Molecular Biology, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Cisplatin combined with hyperthermia kills HepG2 cells in intraoperative blood salvage but preserves the function of erythrocytes - Jin-ting Yang; Li-hui Tang; Yun-qing Liu; Yin Wang; Lie-ju Wang; Feng-jiang Zhang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2015)

A model with leaf area index and apple size parameters for 2.4 GHz radio propagation in apple orchards - Xiu-ming Guo; Xin-ting Yang; Mei-xiang Chen; Ming Li; Yan-an Wang (Precision Agriculture, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Astrocytic glycogenolysis: mechanisms and functions - Leif Hertz; Junnan Xu; Dan Song; Ting Du; Baoman Li; Enzhi Yan; Liang Peng (Metabolic Brain Disease, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Sunitinib mesylate inhibits proliferation of human colonic stromal fibroblasts in vitro and in vivo - Zhan-huai Wang; Qiong Li; Shu-qin Ruan; Qian Xiao; Yue Liu; Ye-ting Hu; Li-feng Hu; Hai-yan Chen; Shu Zheng; Su-zhan Zhang; Ke-feng Ding (Journal of Zhejiang University-SCIENCE B, 2014)

Response of bankfull discharge of the Inner Mongolia Yellow River to flow and sediment factors - Suzhen Hou; Ping Wang; Yan Guo; Ting Li (Journal of Earth System Science, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

The suitability of Ostrinia furnacalis (Lepidoptera: Crambidae) eggs for Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) can be changed by T. ostriniae - Ping Zhu; Yan-Feng Zhang; Qiong-Ting Song; Fan Zhang; Yuan-Xi Li (Applied Entomology and Zoology, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

An approach based on antioxidant fingerprint–efficacy relationship and TLC bioautography assay to quality evaluation of Rubia cordifolia from various sources - Xu-Jie Zhang; Li-Juan Liu; Ting-Ting Song; Yan-Qiu Wang; Xiao-hong Yang (Journal of Natural Medicines, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

RACK1 promotes the proliferation of THP1 acute myeloid leukemia cells - Dalin Zhang; Qingyang Wang; Ting Zhu; Junxia Cao; Xueying Zhang; Jing Wang; Xiaoqian Wang; Yan Li; Beifen Shen; Jiyan Zhang (Molecular and Cellular Biochemistry, 2013)

Introgression of bacterial wilt resistance from eggplant to potato via protoplast fusion and genome components of the hybrids - Yan Yu; Wenxuan Ye; Li He; Xingkui Cai; Ting Liu; Jun Liu (Plant Cell Reports, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Walleye dermal sarcoma virus: expression of a full-length clone or the rv-cyclin (orf a) gene is cytopathic to the host and human tumor cells - Kun Xu; Ting Ting Zhang; Ling Wang; Cun Fang Zhang; Long Zhang; Li Xia Ma; Ying Xin; Chong Hua Ren; Zhi Qiang Zhang; Qiang Yan; Daniel Martineau; Zhi Ying Zhang (Molecular Biology Reports, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Analysis of the genetic effects of prolactin gene polymorphisms on chicken egg production - Hui-Fang Li; Jing-Ting Shu; Yu-Feng Du; Yan-Ju Shan; Kuan-Wei Chen; Xue-Yu Zhang; Wei Han; Wen-Juan Xu (Molecular Biology Reports, 2013)

Expression of MMP-9 in hepatic sinusoidal obstruction syndrome induced by Gynura segetum - Xia-zhen Yu; Tao Ji; Xue-li Bai; Liang Liang; Lin-yan Wang; Wei Chen; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Role of ROS/RhoA/PI3K/PKB Signaling in NS1619-Mediated Blood–Tumor Barrier Permeability Increase - Yan-Ting Gu; Yi-Xue Xue; Yan-Feng Wang; Jin-Hui Wang; Qian-Ru ShangGuan; Jia-Xu Zhang; Li-Juan Qin (Journal of Molecular Neuroscience, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals - Gui Bing Li; Yun Kai Li; Ting Wu Xu; Yao Ze Liu; Hai Jin; Pei Ling Yang; Da Zhuang Yan; Shu Mei Ren; Zhi Fang Tian (Irrigation Science, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Surface topographic characteristics of suspended particulates in reclaimed wastewater and effects on clogging in labyrinth drip irrigation emitters - Yun Kai Li; Yao Ze Liu; Gui Bing Li; Ting Wu Xu; Hai Sheng Liu; Shu Mei Ren; Da Zhuang Yan; Pei Ling Yang (Irrigation Science, 2012)

Prevalence, intensity and associated factor analysis of Tropilaelaps mercedesae infesting Apis mellifera in China - Qi Hua Luo; Ting Zhou; Ping Li Dai; Huai Lei Song; Yan Yan Wu; Qiang Wang (Experimental and Applied Acarology, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Fluorofenidone attenuates renal interstitial fibrosis in the rat model of obstructive nephropathy - Bing-xin Li; Yi-ting Tang; Wei Wang; Yan-yun Xie; Na-sui Wang; Qiong-jing Yuan; Fang-fang Zhang; Zhang-zhe Peng; Gao-yun Hu; Li-jian Tao (Molecular and Cellular Biochemistry, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Novel Approach for Endothelializing Vascular Devices: Understanding and Exploiting Elastin–Endothelial Interactions - Brent D. Wilson; Christopher C. Gibson; Lise K. Sorensen; Margaret Yoklavich Guilhermier; Melissa Clinger; Linda L. Kelley; Yan-Ting E. Shiu; Dean Y. Li (Annals of Biomedical Engineering, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Novel 1-alkyl-tryptophan derivatives downregulate IDO1 and IDO2 mRNA expression induced by interferon-gamma in dendritic cells - Ting Sun; Xiang-Hua Chen; Zheng-De Tang; Jiong Cai; Xiao-Yan Wang; Shih-Chen Wang; Zhao-Long Li (Molecular and Cellular Biochemistry, 2010)

Sevoflurane postconditioning reduces myocardial reperfusion injury in rat isolated hearts via activation of PI3K/Akt signaling and modulation of Bcl-2 family proteins - Li-na Yu; Jing Yu; Feng-jiang Zhang; Mei-juan Yang; Ting-ting Ding; Jun-kuan Wang; Wei He; Tao Fang; Gang Chen; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and characterization of polymorphic microsatellite loci in Aquilaria sinensis (Lour.) Gilg - Yan-Ting Zhang; Zheng-Feng Wang; Hong-Lin Cao; Xiao-Yi Li; Lin-Fang Wu; Shu-Bin Zhuo; Xiao-Feng Huang (Conservation Genetics Resources, 2010)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Electroacupuncture Induced Spinal Plasticity is Linked to Multiple Gene Expressions in Dorsal Root Deafferented Rats - Xu-Yang Wang; Xiao-Li Li; Sun-Quan Hong; Yan-Bin Xi-Yang; Ting-Hua Wang (Journal of Molecular Neuroscience, 2009)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

Mechanism of Iodine Uptake by Cabbage: Effects of Iodine Species and Where It is Stored - Huan-Xin Weng; Chun-Lai Hong; Ai-Lan Yan; Le-Hua Pan; Ya-Chao Qin; Lü-Ting Bao; Ling-Li Xie (Biological Trace Element Research, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Effects of pcDNA3-β-NGF Gene-modified BMSC on the Rat Model of Parkinson’s Disease - Ting-Hua Wang; Zhong-Tang Feng; Peng Wei; Hui Li; Zhen-Jiang Shi; Li-Yan Li (Journal of Molecular Neuroscience, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Induction of experimental acute ulcerative colitis in rats by administration of dextran sulfate sodium at low concentration followed by intracolonic administration of 30% ethanol - Yan Chen; Jian-min Si; Wei-li Liu; Jian-ting Cai; Qin Du; Liang-jing Wang; Min Gao (Journal of Zhejiang University-SCIENCE B, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

System for automatic generalization of topographic maps - Hao-wen Yan; Zhi-lin Li; Ting-hua Ai (Chinese Geographical Science, 2006)

Effect of the Phosphate Group with Different Negative Charges on the Conformation of Phosphorylated Ser/Thr-Pro Motif - Yan-Ting Guo; Yan-Mei Li; Zhen-Tai Zhu; Yu-Fen Zhao (International Journal of Peptide Research and Therapeutics, 2005)